Coating type organic film forming composition, pattern forming method, polymer, and method for producing polymer

By using a polymer containing a ring structure and an organic group to form a organic film with high etching and high twisted resistance, the problem of lack of focus in the optical carvings caused by the height difference between the substrate is solved. Expand the process of process.

CN113359390BActive Publication Date: 2025-01-24SHIN ETSU CHEMICAL CO LTD
View PDF 17 Cites 0 Cited by

Patent Information

Application Number
CN202110240480.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-05
Filing Date
2021-03-04
Publication Date
2025-01-24
Estimated Expiration
2041-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to form an organic film with high bending resistance and dry etch resistance on the substrate, especially when there is a height difference between the substrate, the substrate cannot be effectively flattened, resulting in insufficient focus depth and process margin during the photolithography process. Reduce.

Method used

A polymer containing a specific structure is used as a coating organic film to form a composition. By importing the ring structure and organic base group, it forms an organic film with high etching and high twisted resistance. The polymer is improved by improving solvents, reducing the incidence of defects, and increasing solvents with heat treatment.

Benefits of technology

After the dry etching is performed on the line pattern with a slightly finer and high vertical ratio than 40nm, the collapse or distortion of the line does not occur. Focus depth and process halo.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113359390B_ABST
    Figure CN113359390B_ABST
Patent Text Reader

Abstract

The present invention relates to a composition for forming a coating type organic film, a method for forming a pattern, a polymer, and a method for producing the polymer. The subject of the present invention is to provide a composition for forming a coating type organic film, which is a composition for forming a coating type organic film that can form an organic film with high pattern bending resistance and high dry etching resistance, and has excellent solvent solubility and a low incidence of defects. The present invention provides a composition for forming a coating type organic film, which is characterized by containing: a polymer having a structure represented by the following general formula (1) as a partial structure; and an organic solvent. In formula (1), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may also have a substituent, and W1 is an aromatic group having 6 to 30 carbon atoms which may also have a substituent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a coating type organic film forming composition, a pattern forming method using the composition, a polymer contained in the composition, and a method for producing the polymer. Background Art

[0002] In recent years, with the high integration and high speed of LSI, there is a demand for finer pattern rules. In photolithography using light exposure, which is currently a general technology, various technical developments are being conducted to determine how to perform fine and high-precision pattern processing using the light source used.

[0003] With the reduction of the processing line width, it has been reported that when a hard mask mainly composed of carbon is used as a mask for dry etching of a substrate to be processed, the organic film may be twisted or bent (Non-Patent Document 1). The amorphous carbon (hereinafter referred to as CVD-C) film produced by using CVD or ALD to produce the hard mask can reduce the number of hydrogen atoms in the film, and is generally known to be very effective in preventing the twisting.

[0004] However, if the processed substrate has a height difference, if the processed substrate is used in the subsequent pattern forming step using photolithography with the height difference, the process margin such as the focus depth in the photolithography step will be insufficient. Therefore, it is necessary to use an organic film to flatten the height difference of the substrate. By flattening the processed substrate with an organic film, the thickness variation of the resist lower film or the photoresist upper film formed thereon can be suppressed, the focus depth of the photolithography can be expanded, and the process margin can be expanded.

[0005] However, the CVD-C film using methane gas, ethane gas, acetylene gas, etc. as raw materials is an excellent film for forming an organic film with uniform film thickness on a substrate. However, when there is a height difference on the substrate, if the film thickness does not change with the depth of the height difference to be processed, an organic film with a flat surface cannot be formed. Therefore, the CVD-C film is not suitable as a method for flattening a substrate with a height difference.

[0006] In such a case, if an organic film is formed by spin coating an organic film forming material containing an organic resin, the organic film material can not only fill the height difference of the substrate, but also has the advantage of flattening the substrate surface. However, such an organic film has been used as an organic film for multilayer resist processing in the form of an organic hard mask, but since it uses an organic material as a base material, the distortion performance during fine pattern formation is insufficient compared to a CVD-C film. Therefore, an organic resin for an organic underlayer film having a filling and flattening performance as an organic hard mask and having a distortion resistance equivalent to that of a CVD-C film is sought.

[0007] In addition, as for the conventional technology, Patent Document 1 discloses a fluorene compound having high heat resistance. However, the resin produced by this technology has low solubility and a high risk of defects. Therefore, it is sought to maintain high distortion resistance while improving solvent solubility.

[0008] Prior art literature

[0009] Patent Literature

[0010] [Patent Document 1] Japanese Patent No. 6094947

[0011] Non-patent literature

[0012] [Non-patent document 1] (Proc. Of Symp. Dry. Process, (2005) p11) Summary of the invention

[0013] Problem that the invention aims to solve

[0014] The problem to be solved by the present invention is to provide a composition which is a coating-type organic film-forming composition that can form an organic film with high pattern bending resistance and high dry etching resistance, and has excellent solvent solubility and a low incidence of defects; and to provide a pattern forming method using the composition, a polymer contained in the composition, and a method for manufacturing the polymer.

[0015] Solutions for solving problems

[0016] In order to solve the above-mentioned problems, the present invention provides a coating type organic film-forming composition, characterized in that it contains: a polymer having a structure represented by the following general formula (1) as a partial structure; and

[0017] Organic solvents.

[0018] [Chemistry 1]

[0019]

[0020] In formula (1), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may have a substituent, and W1 is an aryl group having 6 to 30 carbon atoms which may have a substituent.

[0021] By introducing such a partial structure into the main skeleton, the coating film is formed with a condensed aromatic ring structure having high etching resistance, and an organic film having high resistance to pattern bending and dry etching can be formed. In particular, the coating-type organic film-forming composition containing the above-mentioned polymer can form an organic film that does not cause line collapse or distortion after dry etching of a line pattern finer than 40 nm and with a high aspect ratio, and can form a coating film with excellent in-plane uniformity.

[0022] Furthermore, in the structure represented by formula (1), the carbon atom at the top position of the fluorene ring is bonded to the aromatic group W1. Therefore, the carbon atom at the top position of the fluorene ring in one repeating unit represented by formula (1) is bonded to another repeating unit, or to one crosslinking group, or to one terminal group. That is, the carbon atom at the top position of the fluorene ring in the repeating unit represented by formula (1) has one bond number to other atoms or atomic groups not shown in formula (1). The detailed reason is not clear, but a polymer having such a structure represented by formula (1) as a partial structure can exhibit better solvent solubility than a polymer having a polymerization number of 2 carbon atoms at the top position of the fluorene skeleton, and can suppress the occurrence of defects. Furthermore, due to the high solvent solubility, an organic film having excellent filling and planarizing properties can be formed. On the other hand, an organic film formed using the coating type organic film-forming composition of the present invention containing a polymer having a structure represented by formula (1) as a partial structure can exhibit sufficient solvent resistance by heat treatment.

[0023] The present invention also provides a coating type organic film-forming composition comprising: a polymer having a partial structure represented by the following general formula (2); and an organic solvent.

[0024] [Chemistry 2]

[0025]

[0026] In formula (2), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may also have a substituent, W1 is an aromatic group having 6 to 30 carbon atoms which may also have a substituent, W2 is an organic group having at least one aromatic ring, a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms, W2 may also be a part of a repeating unit, and when W2 is the aforementioned organic group, the aforementioned organic group W2 may also be cross-linked with other repeating units.

[0027] By introducing such a partial structure into the main skeleton, the coating film is formed with a condensed aromatic ring structure with high etching resistance, and an organic film with high resistance to pattern bending and dry etching can be formed. In particular, the coating type organic film forming composition contains the above-mentioned polymer, and can form an organic film that does not collapse or twist the line after dry etching of a line pattern finer than 40nm and with a high aspect ratio, and can form a coating film with excellent in-plane uniformity. In addition, by introducing W2, the solvent solubility of the coating type organic film forming composition can be adjusted, and the etching resistance, filling / planarization characteristics and other required performances of the organic film obtained using the coating type organic film forming composition can be adjusted.

[0028] Furthermore, in the structure represented by formula (2), the carbon atom at the top position of the fluorene ring is bonded to the aromatic group W1 and the aforementioned organic group, hydroxyl group or alkyloxy group W2. Therefore, the carbon atom at the top position of the fluorene ring in one repeating unit represented by formula (2) has a bonding number of 0 with other atoms or atomic groups not shown in formula (2). By introducing W2, the molecular weight can be adjusted, thereby improving the solvent solubility. As a result, the polymer having such a partial structure represented by formula (2) can exhibit better solvent solubility than the solvent solubility of the polymer having a polymerization number of 2 of the carbon atoms at the top position of the fluorene skeleton, and can suppress the occurrence of defects. Furthermore, due to the high solvent solubility, an organic film that can exhibit excellent filling and planarization characteristics can be formed. On the other hand, the organic film formed by the coating-type organic film-forming composition of the present invention containing the polymer having the partial structure represented by formula (2) can exhibit sufficient solvent resistance by heat treatment.

[0029] In the above formula (2), the above W2 is the above organic group and preferably contains a nitrogen atom.

[0030] A composition containing such an ideal polymer not only improves solvent solubility, but also can form an organic film that does not twist after dry etching of a line pattern finer than 40 nm and having a high aspect ratio, although the detailed reason is not yet clear.

[0031] Furthermore, the polymer having the partial structure represented by the formula (1) or (2) described above preferably has a partial structure represented by the following general formula (3).

[0032] [Chemistry 3]

[0033]

[0034] In formula (3), the ring structures Ar1 and Ar2 are the aforementioned ring structures Ar1 and Ar2, and W3 is a hydrogen atom.

[0035] When an organic film formed from an organic film-forming composition containing a polymer having a partial structure represented by the general formula (3) is heated, a crosslinking reaction occurs due to a coupling reaction involving dehydrogenation of hydrogen atoms at trityl positions on the fluorene ring.

[0036] The weight average molecular weight of the aforementioned polymer is preferably 500 to 5,000.

[0037] When the organic film-forming composition contains a polymer having a weight average molecular weight within such a range, outgassing during baking can be suppressed without impairing solubility in an organic solvent.

[0038] The organic solvent is preferably a mixture of one or more organic solvents having a boiling point of less than 160°C and one or more organic solvents having a boiling point of 160°C or higher.

[0039] When the organic solvent is the mixture, thermal fluidity is imparted to the organic film by adding a high boiling point solvent to the polymer, so that the organic film forming composition has both higher filling and planarizing properties.

[0040] The aforementioned coating type organic film-forming composition preferably further contains one or more of an acid generator, a crosslinking agent, a surfactant and a plasticizer.

[0041] If the organic film-forming composition contains such an additive, the coating property and the filling / planarization characteristics will be more excellent.

[0042] The present invention provides a pattern forming method, which is characterized by: forming an organic film on a workpiece using the organic film forming composition of the present invention, forming a silicon-containing resist underlayer film on the organic film using a silicon-containing resist underlayer film material, forming a resist upper layer film on the silicon-containing resist underlayer film using a photoresist composition, forming a circuit pattern on the resist upper layer film, using the aforementioned resist upper layer film on which the pattern has been formed as a mask, etching the aforementioned silicon-containing resist underlayer film, transferring the pattern to the silicon-containing resist underlayer film, using the aforementioned silicon-containing resist underlayer film to which the pattern has been transferred as a mask, etching the aforementioned organic film, transferring the pattern to the organic film, and further using the aforementioned organic film to which the pattern has been transferred as a mask, etching the aforementioned workpiece to form a pattern on the workpiece.

[0043] The pattern forming method using the three-layer resist process can form a fine pattern on the processed substrate with high precision. In particular, the organic film is formed using the coating-type organic film-forming composition of the present invention in the pattern forming method, so that an organic film with high resistance to pattern bending and high resistance to dry etching can be formed, and the occurrence of defects can be suppressed.

[0044] Furthermore, the present invention provides a pattern forming method, characterized in that: an organic film is formed on a workpiece using the coating-type organic film forming composition of the present invention, a silicon-containing resist underlayer film is formed on the organic film using a silicon-containing resist underlayer film material, an organic antireflection film (BARC) is formed on the silicon-containing resist underlayer film, a photoresist composition is used on the organic antireflection film to form a resist upper film to form a four-layer film structure, a circuit pattern is formed on the resist upper film, the patterned resist upper film is used as a mask to etch the organic antireflection film and the silicon-containing resist underlayer film, the pattern is transferred to the organic antireflection film and the silicon-containing resist underlayer film, the silicon-containing resist underlayer film to which the pattern is transferred is used as a mask to etch the organic film to transfer the pattern to the organic film, and further, the organic film to which the pattern is transferred is used as a mask to etch the workpiece to form a pattern on the workpiece.

[0045] The pattern forming method using the four-layer resist process can form a fine pattern on the processed substrate with higher precision. In particular, the organic film is formed using the coating-type organic film-forming composition of the present invention in the pattern forming method, so that an organic film with high resistance to pattern bending and high resistance to dry etching can be formed, and the occurrence of defects can be suppressed.

[0046] Furthermore, the present invention provides a pattern forming method, characterized in that: an organic film is formed on a workpiece using the coating-type organic film forming composition of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film is formed on the organic film, a photoresist composition is used on the inorganic hard mask to form a resist upper film, a circuit pattern is formed on the resist upper film, the aforementioned resist upper film with the pattern formed is used as a mask to etch the aforementioned inorganic hard mask, the pattern is transferred to the inorganic hard mask, the aforementioned inorganic hard mask with the pattern transferred is used as a mask to etch the aforementioned organic film, the pattern is transferred to the organic film, and further, the aforementioned workpiece is etched using the organic film with the pattern transferred as a mask to form a pattern on the workpiece.

[0047] The pattern forming method using the three-layer resist process can form a fine pattern on the processed substrate with high precision. In particular, the organic film is formed using the coating type organic film forming composition of the present invention in the aforementioned pattern forming method, so that an organic film with high pattern bending resistance and high dry etching resistance can be formed, and the occurrence of defects can be suppressed.

[0048] Furthermore, the present invention provides a pattern forming method, characterized in that: an organic film is formed on a workpiece using the coating-type organic film forming composition of the present invention, an inorganic hard mask selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film is formed on the organic film, an organic anti-reflective film is formed on the inorganic hard mask, a photoresist composition is used on the organic anti-reflective film to form a resist upper film to form a four-layer film structure, a circuit pattern is formed on the resist upper film, the organic anti-reflective film and the inorganic hard mask are etched using the patterned resist upper film as a mask, and the pattern is transferred to the organic anti-reflective film and the inorganic hard mask, the organic film is etched using the patterned inorganic hard mask as a mask, and the pattern is transferred to the organic film, and further, the workpiece is etched using the patterned organic film as a mask to form a pattern on the workpiece.

[0049] The pattern forming method using the four-layer resist process can form a fine pattern on the processed substrate with higher precision. In particular, the pattern forming method uses the coating type organic film forming composition of the present invention to form an organic film, so that an organic film with high pattern bending resistance and high dry etching resistance can be formed, and the occurrence of defects can be suppressed.

[0050] The inorganic hard mask is preferably formed by a CVD method or an ALD method.

[0051] When the inorganic hard mask is formed by a CVD method or an ALD method, a fine pattern can be formed on a substrate to be processed with higher precision.

[0052] The method of forming the circuit pattern on the resist upper layer film is preferably optical lithography using light with a wavelength of 10 nm to 300 nm, direct drawing using an electron beam, nanoimprinting, or a combination thereof.

[0053] When the above method is used as a method for forming a circuit pattern on the resist upper layer film, a fine pattern can be formed on the substrate to be processed with higher accuracy.

[0054] The above-mentioned method for forming a pattern of the resist upper layer film preferably includes alkali development or development using an organic solvent.

[0055] When alkali development or development using an organic solvent is used as the development method, a fine pattern can be formed on the substrate to be processed with higher precision.

[0056] As the object to be processed, a semiconductor device substrate, a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film or a metal oxide nitride film is preferably used.

[0057] In the present invention, the object to be processed may be, for example, the one described above.

[0058] The aforementioned object to be processed preferably includes silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, molybdenum or an alloy thereof.

[0059] As the aforementioned metals, any of these can be used.

[0060] The present invention also provides a polymer having a partial structure represented by the following general formula (1).

[0061] [Chemistry 4]

[0062]

[0063] In formula (1), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may have a substituent, and W1 is an aryl group having 6 to 30 carbon atoms which may have a substituent.

[0064] The polymer is a component of an organic film forming composition that can provide an organic film formed of a condensed aromatic ring structure with high etching resistance, and thus an organic film with high pattern bending resistance and high dry etching resistance. By using the polymer, an organic film can be formed that does not cause line collapse or distortion after dry etching of a line pattern finer than 40 nm and with a high aspect ratio, and in particular, a coating film with excellent in-plane uniformity can be formed.

[0065] Furthermore, as described above, the carbon atom at the top position of the fluorene ring in the repeating unit represented by formula (1) has a bonding number of 1 with other atoms or atomic groups not shown in formula (1). The detailed reason is still unclear, but the polymer of the present invention having a structure represented by formula (1) as a partial structure can exhibit better solvent solubility than a polymer having a polymerization number of 2 carbon atoms at the top position of the fluorene skeleton, and can suppress the occurrence of defects. Furthermore, due to the high solvent solubility, an organic film that can exhibit excellent filling and planarization properties can be formed. On the other hand, a polymer having a structure represented by formula (1) as a partial structure can exhibit sufficient solvent resistance by heat treatment.

[0066] The present invention also provides a polymer having a partial structure represented by the following general formula (2).

[0067] [Chemistry 5]

[0068]

[0069] In formula (2), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may also have a substituent, W1 is an aromatic group having 6 to 30 carbon atoms which may also have a substituent, W2 is an organic group having at least one aromatic ring, a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms, W2 may also be a part of a repeating unit, and when W2 is the aforementioned organic group, the aforementioned organic group W2 may also be cross-linked with other repeating units.

[0070] The polymer is a component of an organic film forming composition that can form an organic film formed of a condensed aromatic ring structure with high etching resistance, and thus can provide an organic film with high pattern bending resistance and high dry etching resistance. In particular, by using the polymer, an organic film can be formed that does not cause line collapse or distortion after dry etching of a line pattern finer than 40nm and with a high aspect ratio, and in particular, a coating film with excellent in-plane uniformity can be formed. In addition, by introducing a partial structure such as the polymer into the main skeleton, the solvent solubility of the polymer can be adjusted, and it will become a component of an organic film forming composition that can form an organic film with adjusted required performance such as etching resistance and filling / planarization characteristics of the organic film formed using the polymer.

[0071] Furthermore, as described above, the carbon atom at the top position of the fluorene ring in one repeating unit represented by formula (2) has a bonding number of 0 with other atoms or atomic groups not shown in formula (2). The detailed reason is still unclear, but a polymer having such a partial structure represented by formula (2) can exhibit better solvent solubility and suppress the occurrence of defects than a polymer having a polymerization number of 2 carbon atoms at the top position of the fluorene skeleton. Furthermore, due to the high solvent solubility, an organic film that can exhibit excellent filling and planarization properties can be formed. On the other hand, a polymer having a partial structure represented by formula (2) can exhibit sufficient solvent resistance by heat treatment.

[0072] In the above formula (2), the above W2 is the above organic group and preferably contains a nitrogen atom.

[0073] By using such an ideal polymer, not only can the solvent solubility be improved, but also an organic film that does not twist after dry etching of a line pattern finer than 40 nm and having a high aspect ratio can be formed, although the detailed reason is not yet clear.

[0074] The polymer having the partial structure represented by the formula (1) or (2) described above preferably further has a partial structure represented by the following general formula (3).

[0075] [Chemistry 6]

[0076]

[0077] In formula (3), the ring structures Ar1 and Ar2 are the aforementioned ring structures Ar1 and Ar2, and W3 is a hydrogen atom.

[0078] If the polymer further has the partial structure, it can become a component of an organic film-forming composition capable of forming an organic film having higher bending resistance and higher dry etching resistance.

[0079] The weight average molecular weight of the aforementioned polymer is preferably 500 to 5,000.

[0080] When the organic film-forming composition contains a polymer having a weight average molecular weight within such a range, outgassing during baking can be suppressed without impairing solubility in an organic solvent.

[0081] The present invention also provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (1), characterized in that: a fluorenol having the above-mentioned aromatic group W1 and a tertiary alcohol group is used as a monomer, and the above-mentioned polymer is synthesized by utilizing an electrophilic substitution reaction of the fluorenyl ring accompanied by dehydration.

[0082] According to this production method, a polymer having a partial structure represented by the above general formula (1) can be produced.

[0083] Furthermore, the present invention provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (2), characterized in that: the aforementioned W2 is the aforementioned organic group, and the synthesis of the aforementioned polymer is carried out by copolymerizing a fluorenol having the aforementioned aromatic group W1 and a tertiary alcohol group with a compound having the aforementioned organic group W2 as a partial structure.

[0084] According to the production method, a polymer having a partial structure represented by the general formula (2) in which the W2 is the organic group can be produced.

[0085] Furthermore, the present invention provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (2), characterized in that: the aforementioned W2 is the aforementioned organic group, a fluorenol having the aforementioned aromatic group W1 and a tertiary alcohol group is used as a monomer, the synthesis of the aforementioned polymer is carried out by utilizing an electrophilic substitution reaction of the fluorenyl ring accompanied by dehydration, and a compound having the aforementioned organic group W2 as a partial structure is added during the synthesis of the aforementioned polymer.

[0086] According to the production method, a polymer having a partial structure represented by the general formula (2) in which the W2 is the organic group can be produced.

[0087] The present invention also provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (2), characterized in that: the aforementioned W2 is a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms, a fluorenol having the aforementioned aromatic group W1 and a tertiary alcohol group is used as a monomer, the aforementioned polymer is synthesized by utilizing an electrophilic substitution reaction of the fluorenyl ring accompanied by dehydration, and water or alcohol is pre-added to the reaction system before or during the aforementioned synthesis.

[0088] According to the production method, a polymer having a partial structure represented by the general formula (2) in which W2 is a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms can be produced.

[0089] The present invention also provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (3), characterized in that: a fluorenol having the above-mentioned aromatic group W1 and a tertiary alcohol group is copolymerized with a fluorenol having a secondary alcohol group.

[0090] According to the production method, a polymer having a partial structure represented by the above general formula (3) can be produced.

[0091] The present invention also provides a method for producing a polymer, which is a method for producing a polymer having a partial structure represented by the above-mentioned general formula (3), characterized in that: using one of the first fluorenols having the above-mentioned aromatic group W1 and a tertiary alcohol group or the second fluorenols having a secondary alcohol group as a monomer, synthesizing the above-mentioned polymer by utilizing an electrophilic substitution reaction of the fluorene ring accompanied by dehydration to obtain a first polymer, adding the other of the first fluorenol and the second fluorenol to the above-mentioned first polymer, and further polymerizing to obtain a polymer having the partial structure represented by the above-mentioned general formula (3) as a second polymer.

[0092] According to the production method, a polymer having a partial structure represented by the above general formula (3) can be produced.

[0093] Effects of the Invention

[0094] As described above, the coating type organic film forming composition of the present invention can form an organic film with high dry etching resistance, and in particular, can form an organic film that does not collapse or twist the line after dry etching of a line pattern that is finer than 40nm and has a high aspect ratio. In addition, by improving the solvent solubility of the polymer, the risk of defects can be reduced. Therefore, the coating type organic film forming composition of the present invention can form an organic film that is useful and excellent in the manufacturing steps of semiconductor devices. In addition, the polymer of the present invention is most suitable for the components of the above-mentioned composition. BRIEF DESCRIPTION OF THE DRAWINGS

[0095] [ Figure 1 ] is an explanatory diagram of an example of a pattern forming method utilizing a three-layer resist method of the present invention. DETAILED DESCRIPTION

[0096] Hereinafter, the present invention will be described in detail, but the present invention is not limited thereto.

[0097] <Polymer>

[0098] The present invention is a polymer characterized by having a structure represented by the following general formula (1) as a partial structure.

[0099] [Chemistry 7]

[0100]

[0101] In formula (1), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may have a substituent, and W1 is an aryl group having 6 to 30 carbon atoms which may have a substituent. The ring structures Ar1 and Ar2 may be the same or different from each other.

[0102] By introducing such a partial structure into the main skeleton, the coating film is formed with a condensed aromatic ring structure having high etching resistance, and an organic film having high resistance to pattern bending and dry etching can be formed. The organic film formed using the polymer of the present invention can be a coating film having excellent in-plane uniformity, especially after dry etching of a line pattern finer than 40 nm and having a high aspect ratio, by containing the above polymer.

[0103] Furthermore, in the structure represented by formula (1), the carbon atom at the top position of the fluorene ring is bonded to the aromatic group W1. Therefore, the carbon atom at the top position of the fluorene ring in one repeating unit represented by formula (1) is bonded to another repeating unit, or to one crosslinking group, or to one terminal group. That is, the carbon atom at the top position of the fluorene ring in the repeating unit represented by formula (1) has one bond number to other atoms or atomic groups not shown in formula (1). The detailed reason is not clear, but a polymer having such a structure represented by formula (1) as a partial structure can exhibit better solvent solubility than a polymer having a polymerization number of 2 carbon atoms at the top position of the fluorene skeleton, and can suppress the occurrence of defects. Furthermore, due to the high solvent solubility, an organic film having excellent filling and planarizing properties can be formed. On the other hand, an organic film formed using a polymer having a structure represented by formula (1) as a partial structure can develop sufficient solvent resistance by heat treatment.

[0104] The partial structure composed of Ar1 and Ar2 of the polymer in the general formula (1) above can be exemplified by the following. Such aromatic rings may also have substituents such as vinyl, ethynyl, ethynylphenyl, allyl, propargyl, aryl, allyloxy, propargyloxy, etc. Among the following, fluorene and benzofluorene structures are preferred in terms of the ease of obtaining raw materials.

[0105] [Chemistry 8]

[0106]

[0107] Furthermore, the present invention is a polymer having a partial structure represented by the following general formula (2).

[0108] [Chemistry 9]

[0109]

[0110] In formula (2), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may also have a substituent, W1 is an aryl group having 6 to 30 carbon atoms which may also have a substituent, W2 is an organic group having at least one aromatic ring, a hydroxyl group, or an alkyloxy group having 1 to 10 carbon atoms, W2 may also be a part of a repeating unit, and when W2 is the aforementioned organic group, the aforementioned organic group W2 may also be cross-linked with other repeating units. In addition, the ring structures Ar1 and Ar2 may be the same or different from each other.

[0111] By introducing such a partial structure into the main skeleton, the coating film is formed with a condensed aromatic ring structure with high etching resistance, and an organic film with high resistance to pattern bending and dry etching can be formed. The organic film formed using the polymer of the present invention can be formed by containing the above-mentioned polymer, which can suppress the occurrence of line collapse and distortion after dry etching of a line pattern finer than 40nm and with a high aspect ratio, and has excellent in-plane uniformity. In addition, by introducing W2, the solvent solubility of the polymer, the etching resistance of the organic film formed using the polymer can be adjusted, and the required performance such as the filling / planarization characteristics can be adjusted.

[0112] Furthermore, in the structure represented by formula (2), the carbon atom at the top position of the fluorene ring is bonded to the aromatic group W1, and the aforementioned organic group, hydroxyl group or alkyloxy group W2. Therefore, the carbon atom at the top position of the fluorene ring in one repeating unit represented by formula (2) has a bonding number of 0 with other atoms or atomic groups not shown in formula (2). By introducing W2, the molecular weight can be adjusted, thereby improving the solvent solubility. As a result, a polymer having a structure represented by such formula (2) as a partial structure can exhibit better solvent solubility than the solvent solubility of a polymer having a polymerization number of 2 for the carbon atoms at the top position of the fluorene skeleton, and can suppress the occurrence of defects. Furthermore, due to the high solvent solubility, an organic film that can exhibit excellent filling and planarization characteristics can be formed. On the other hand, an organic film formed using a polymer having a partial structure represented by formula (2) can exhibit sufficient solvent resistance by heat treatment.

[0113] In addition, as described above, the carbon atom at the top position of the fluorene ring in one repeating unit represented by the above formula (1) is bonded to another repeating unit, or to one crosslinking group, or to one terminal group. Therefore, the partial structure represented by the above formula (2) is an example of the partial structure represented by the above formula (1). That is, the polymer having the partial structure represented by the above formula (2) is an example of a polymer having the structure represented by the above formula (1) as a partial structure.

[0114] The organic group having one or more aromatic rings in W2 in the general formula (2) may be exemplified by the following, and such aromatic rings may also have substituents such as vinyl, ethynyl, ethynylphenyl, allyl, propargyl, aryl, allyloxy, propargyloxy, etc. Considering the viewpoint of imparting etching resistance and solvent solubility, the organic group is preferably one having a naphthalene ring, a fluorene structure, or a carbazole structure. In addition, the organic groups exemplified below may be bonded to the carbon atom at the top position of the fluorene ring of formula (2) at any position.

[0115] [Chemistry 10]

[0116]

[0117] [Chemistry 11]

[0118]

[0119] [Chemistry 12]

[0120]

[0121] The organic group W2 preferably contains a nitrogen atom. By using a polymer having an organic group W2 containing a nitrogen atom introduced into a partial structure, not only can the solvent solubility be improved, but also an organic film that is less likely to be distorted after dry etching of a line pattern finer than 40 nm and with a high aspect ratio can be formed.

[0122] When W2 is a hydroxyl group or an alkyloxy group, a crosslinking reaction occurs due to an electrophilic substitution reaction accompanied by the detachment of the hydroxyl group or the alkyloxy group. This allows the coating film to be formed with a condensed aromatic ring structure having higher etching resistance, thereby forming an organic film having higher bending resistance and higher dry etching resistance.

[0123] Furthermore, the polymer having the partial structure represented by the formula (1) or (2) described above preferably has a partial structure represented by the following general formula (3).

[0124] [Chemistry 13]

[0125]

[0126] In formula (3), the ring structures Ar1 and Ar2 are the aforementioned ring structures Ar1 and Ar2, and W3 is a hydrogen atom.

[0127] When an organic film formed of a polymer having a partial structure represented by the general formula (3) is heated, a cross-linking reaction occurs due to a coupling reaction involving dehydrogenation of hydrogen atoms at trityl positions on the fluorene ring.

[0128] When W3 in the general formula (3) is a hydrogen atom, excellent etching resistance and solvent solubility can be imparted.

[0129] In addition, the Mw (weight average molecular weight) of the aforementioned polymer is preferably 500 to 5000, and the aforementioned Mw is more preferably 600 to 4000. If it is such a molecular weight, solubility in organic solvents can be ensured, and sublimates generated during baking can be suppressed. In addition, the thermal fluidity of the organic film forming composition becomes good, so the fine structure formed on the substrate can be well buried with the aforementioned organic film forming composition, not only that, but also an organic film with a flat substrate as a whole can be formed. In addition, in the present invention, the weight average molecular weight is a polystyrene conversion value determined by GPC (gel permeation chromatography) using THF (tetrahydrofuran) as a developing solvent.

[0130] <Method for producing polymer>

[0131] [Polymer having a partial structure of the general formula (1)]

[0132] An example of the method for producing a polymer having a structure represented by the general formula (1) as a partial structure of the present invention is the following method of using a fluorenol having a tertiary alcohol group, that is, a fluorenol having an aromatic group W1 and a tertiary alcohol group as a monomer and performing an electrophilic substitution reaction on a fluorene ring accompanied by dehydration. Ar1, Ar2 and W1 in the following formula are the same as those described above.

[0133] [Chemistry 14]

[0134]

[0135] The synthesis of the above-mentioned polymer may be carried out using a single fluorenol or using two or more different fluorenols.

[0136] The polymer can be obtained in the presence of an acid catalyst in an organic solvent at room temperature or under cooling or heating as required. As the acid catalyst used, inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropolyacids; organic acids such as oxalic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid; and Lewis acids such as aluminum trichloride, aluminum ethoxide, aluminum isopropoxide, boron trifluoride, boron trichloride, boron tribromide, tin tetrachloride, tin tetrabromide, dibutyltin dichloride, dibutyltin dimethoxide, dibutyltin oxide, titanium tetrachloride, titanium tetrabromide, titanium (IV) methoxide, titanium (IV) ethoxide, titanium (IV) isopropoxide, and titanium (IV) oxide.

[0137] The solvent used is not particularly limited, and examples thereof include: alcohols such as methanol, ethanol, isopropanol, butanol, ethylene glycol, propylene glycol, diethylene glycol, glycerol, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; ethers such as diethyl ether, dibutyl ether, diethylene glycol diethyl ether, diethylene glycol dimethyl ether, tetrahydrofuran, and 1,4-dioxane; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; hydrocarbons such as hexane, heptane, benzene, toluene, xylene, and cumene; nitriles such as acetonitrile; ketones such as acetone, methyl ethyl ketone, and isobutyl methyl ketone; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; and aprotic polar solvents such as dimethyl sulfoxide, N,N-dimethylformamide, and hexamethylphosphoric triamide. These solvents can be used alone or in combination of two or more.

[0138] As for the reaction method, there are the following methods: adding fluorenols and an acid catalyst as a catalyst at once; after dispersing or dissolving the fluorenols, adding the catalyst at once or in portions, or diluting the catalyst with a solvent and adding dropwise; after dispersing or dissolving the catalyst, adding the fluorenols at once or in portions, or diluting the fluorenols with a solvent and adding dropwise. After the reaction is completed, the reactants may be diluted with an organic solvent to remove the catalyst used in the reaction, and then separated and washed to recover the target product.

[0139] The organic solvent used at this time is not particularly limited as long as it can dissolve the target substance and separate into two layers when mixed with water. For example, hydrocarbons such as hexane, heptane, benzene, toluene, and xylene; esters such as ethyl acetate, n-butyl acetate, and propylene glycol methyl ether acetate; ketones such as methyl ethyl ketone, methyl amyl ketone, cyclohexanone, and methyl isobutyl ketone; ethers such as diethyl ether, diisopropyl ether, methyl tert-butyl ether, and ethyl cyclopentyl methyl ether; chlorine-based solvents such as dichloromethane, chloroform, dichloroethane, and trichloroethylene; and mixtures thereof. The washing water used at this time is usually deionized water or ultrapure water. The number of washing times can be one or more. Even if washing is performed more than 10 times, the corresponding washing effect may not be obtained, so it is preferably about 1 to 5 times.

[0140] In order to remove the acidic components in the system during separation and washing, an alkaline aqueous solution may be used for washing. Specific examples of the base include alkali metal hydroxides, alkali metal carbonates, alkaline earth metal hydroxides, alkaline earth metal carbonates, ammonia, and organic ammonium.

[0141] In addition, in order to remove metal impurities or alkaline components in the system during liquid separation and washing, an acidic aqueous solution can also be used for washing. Specific examples of the acid include inorganic acids such as hydrochloric acid, hydrobromic acid, sulfuric acid, nitric acid, phosphoric acid, and heteropoly acids; and organic acids such as oxalic acid, fumaric acid, maleic acid, trifluoroacetic acid, methanesulfonic acid, benzenesulfonic acid, p-toluenesulfonic acid, and trifluoromethanesulfonic acid.

[0142] The above-mentioned liquid separation and washing using the alkaline aqueous solution and the acidic aqueous solution may be performed alone or in combination. From the viewpoint of removing metal impurities, the liquid separation and washing are preferably performed in the order of the alkaline aqueous solution and the acidic aqueous solution.

[0143] After the aforementioned separation and washing using alkaline aqueous solution or acidic aqueous solution, it is also possible to continue washing using neutral water. The washing frequency only needs to be performed once or more, preferably about 1 to 5 times. Neutral water can use the above-mentioned deionized water, ultrapure water, etc. The washing frequency can be once or more, but if the frequency is less, there may be a situation where the alkaline component and the acidic component cannot be removed. Even if washing is performed more than 10 times, the corresponding washing effect may not be obtained, so it is preferably about 1 to 5 times.

[0144] In addition, the reaction product after the liquid separation operation can also be recovered in the form of powder by concentrating the solvent to dryness or performing a crystallization operation under reduced pressure or normal pressure. In order to improve the operability when preparing the organic film forming composition, it can also be prepared in advance into a solution state of appropriate concentration. The concentration at this time is preferably 0.1 to 50% by weight, and more preferably 0.5 to 30% by weight. If it is such a concentration, the viscosity is not easy to increase, so it can prevent damage to the operability, and the amount of the solvent will not be too large, so it is economical.

[0145] The solvent in this case is not particularly limited as long as it can dissolve the polymer. Specific examples include ketones such as cyclohexanone and methyl-2-pentyl ketone; alcohols such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol, and 1-ethoxy-2-propanol; ethers such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether, and diethylene glycol dimethyl ether; and esters such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate, ethyl pyruvate, butyl acetate, methyl 3-methoxypropionate, ethyl 3-ethoxypropionate, tert-butyl acetate, tert-butyl propionate, and propylene glycol mono-tert-butyl ether acetate. These may be used alone or in combination of two or more.

[0146] [Polymer having a partial structure of the general formula (2)]

[0147] {W2 is a polymer having an organic group having an aromatic ring}

[0148] The polymer having a partial structure represented by the general formula (2) of the present invention, when W2 has at least one aromatic ring, can be produced by the following method, etc.: copolymerizing the fluorenols used as the raw material for producing the polymer having a partial structure represented by the general formula (1) with a compound having an organic group W2 as a partial structure; or in the reaction of the polymer having a partial structure represented by the general formula (1), adding a compound having an organic group W2 as a partial structure to perform terminal capping. Ar1, Ar2, W1, and W2 in the following formula are the same as those described above.

[0149] [Chemistry 15]

[0150] (Copolymerization method)

[0151]

[0152] (Terminal Capping Method)

[0153]

[0154] When the above reaction is carried out using a compound containing an organic group having one or more aromatic rings as W2, the compound having a partial structure of W2 acts as a terminal stopper for the fluorenol polymer during the polymerization process. During the reaction, there is a possibility that the aromatic ring of the compound having a partial structure of W2 reacts with a fluorenol polymer having a different chain length as shown below, but for convenience in the present invention, it is marked as in the general formula (2). Ar1, Ar2, W1 and W2 are the same as described above, and n1, n2 and n3 are integers greater than 1.

[0155] [Chemistry 16]

[0156]

[0157] By copolymerizing or terminal-capping the compound containing the partial structure of W2, the molecular weight can be adjusted, and thus the solvent solubility can be improved.

[0158] The reaction and recovery methods of the polymer having a partial structure represented by the general formula (2) are the same as the reaction and recovery methods of the polymer having a partial structure represented by the general formula (1).

[0159] {W2 is a polymer of hydroxyl or alkyloxy}

[0160] In addition, in the polymer having a partial structure represented by the general formula (2) of the present invention, when W2 is a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms, it can be produced by adding water or an alcohol to the reaction system in advance or by adding water or an alcohol during the reaction. In the following formula, R is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms. That is, the group OR in the following formula is W2 in the formula (2). Ar1, Ar2, and W1 are the same as those described above.

[0161] [Chemistry 17]

[0162] (Copolymerization method)

[0163]

[0164] (Multi-stage polymerization method)

[0165]

[0166] In the aforementioned polymerization, similar to the reaction of fluorenols with a compound containing an organic group having one or more aromatic rings as W2, there is a possibility that a fluorenol polymer generated by polymerization on the aromatic rings of Ar1 and Ar2 of the fluorenols may react, for example, as shown in the following formula, but for the sake of convenience in the present invention, it is marked as chemical formula (2). Ar1 and Ar2 are the same as those described above, n1, n2, and n3 are integers greater than 1, and R is a hydrogen atom or an alkyl group having 1 to 10 carbon atoms.

[0167] [Chemistry 18]

[0168]

[0169] In the case of a polymer, when W2 is a hydroxyl group or an alkyloxy group having 1 to 10 carbon atoms, the molecular weight can be adjusted and the introduction of a heteroatom can improve the solvent solubility.

[0170] The reaction and recovery methods of the above-mentioned polymer are the same as those of the polymer having a partial structure represented by the general formula (1).

[0171] [Polymer having a partial structure of the general formula (3)]

[0172] The polymer having a partial structure represented by the general formula (3) of the present invention can be prepared by the following methods: fluorenols and fluorenols having a secondary alcohol group, which are raw materials for producing the polymer having a partial structure represented by the general formula (1), are added at once for copolymerization; or the first fluorenols or the second fluorenols having a secondary alcohol group, which are raw materials for producing the polymer having a partial structure represented by the general formula (1), are polymerized in the first stage, and then a fluorenol different from that in the first stage is added in the second stage for polymerization. When the polymerization is carried out in two stages, a plurality of fluorenols may be mixed and used in the polymerization of the first stage or the second stage, and the same or other fluorenols as those in the third stage or the fourth stage may be further added for polymerization.

[0173] [Chemistry 19]

[0174] (Copolymerization method)

[0175]

[0176] (Multi-stage polymerization method)

[0177]

[0178] In the aforementioned polymerization, similar to the reaction of fluorenols with a compound containing an organic group having one or more aromatic rings as W2, there is a possibility that the fluorenol polymer generated by the polymerization on the aromatic rings of Ar1 and Ar2 of the fluorenols may react, for example, as shown in the following formula, but for the sake of convenience in the present invention, it is marked as chemical formula (3). Ar1, Ar2, W1 are the same as above, and n1, n2, n3 are integers greater than 1.

[0179] [Chemistry 20]

[0180]

[0181] In the polymerization of the polymer having a partial structure represented by the general formula (1) of the present invention, in addition to using fluorenols having an aromatic group W1 and a tertiary alcohol group, fluorenols having W2 or W3 in the partial structure can also be used in combination according to the required performance. Specifically, a side chain structure that contributes to the improvement of the planarization characteristics and a rigid aromatic ring structure that contributes to the improvement of etching resistance and heat resistance can also be used. The raw materials can be combined in any proportion according to the required performance. In addition, the method for manufacturing the polymer can also be selected in accordance with the required performance, and the structure of the polymer such as random and alternating polymerization can be controlled by appropriately selecting copolymerization, multi-stage polymerization, and end-to-end polymerization methods. The composition for forming an organic film using these polymers can take into account the filling / planarization characteristics, heat resistance, distortion resistance, and etching resistance in a high-dimensional manner.

[0182] As described above, if the polymer of the present invention has a partial structure represented by the general formula (1) or (2), or has a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3), it can provide an organic film forming composition that exhibits high etching resistance, excellent distortion resistance, and has a low defect incidence rate due to excellent solvent solubility.

[0183] <Coating type organic film forming composition>

[0184] The present invention also provides a coating-type organic film-forming composition comprising: a polymer having a partial structure represented by the general formula (1) or (2), or having a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3); and an organic solvent. In the coating-type organic film-forming composition of the present invention, the polymer having a partial structure represented by the general formula (1) or (2), or having a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3) can be used alone or in combination of two or more.

[0185] The coating type organic film forming composition of the present invention may further contain a compound for compounding, another polymer or other modifier. The modifier contained in the coating type organic film forming composition of the present invention has the effect of improving the film forming property of spin coating and the filling property on the substrate with height difference. Examples of such modifiers include phenol, o-cresol, m-cresol, p-cresol, 2,3-dimethylphenol, 2,5-dimethylphenol, 3,4-dimethylphenol, 3,5-dimethylphenol, 2,4-dimethylphenol, 2,6-dimethylphenol, 2,3,5-trimethylphenol, 3,4,5-trimethylphenol, 2-tert-butylphenol, 3-tert-butylphenol, 4-tert-butylphenol, 2-phenylphenol, 3-phenylphenol, 4-phenylphenol, 3,5-diphenylphenol, 2-naphthylphenol, 3-naphthylphenol, 4-naphthylphenol, 4-tritylphenol, Resorcinol, 2-methylresorcinol, 4-methylresorcinol, 5-methylresorcinol, catechol, 4-tert-butylcatechol, 2-methoxyphenol, 3-methoxyphenol, 2-propylphenol, 3-propylphenol, 4-propylphenol, 2-isopropylphenol, 3-isopropylphenol, 4-isopropylphenol, 2-methoxy-5-methylphenol, 2-tert-butyl-5-methylphenol, gallol, thymol, isothymol, 4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,2'-dimethyl-4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,2'-diallyl-4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,2'-difluoro-4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,2'-diphenyl-4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,2'-dimethoxy-4,4'-(9H-fluorene-9-ylidene)bisphenol, 2,3,2',3'-tetrahydro-(1,1')-spirobiindene-6,6'-diol, 3,3,3',3'-tetramethyl-2,3,2',3'-tetrahydro-(1,1')-spirobiindene-6,6'-diol, 3,3,3' ,3',4,4'-hexamethyl-2,3,2',3'-tetrahydro-(1,1')-spirobiindene-6,6'-diol, 2,3,2',3'-tetrahydro-(1,1')-spirobiindene-5,5'-diol, 5,5'-dimethyl-3,3,3',3'-tetramethyl-2,3,2',3'-tetrahydro-(1,1')-spirobiindene-6,6'-diol, 1-naphthol, 2-naphthol, 2-methyl-1-naphthol, 4-methoxy-1-naphthol, 7-methoxy-2-naphthol and 1,5-dihydroxynaphthalene, 1,7-dihydroxynaphthalene, 2,dihydroxynaphthalene such as 6-dihydroxynaphthalene, methyl 3-hydroxynaphthalene-2-carboxylate, indene, hydroxyindene, benzofuran, hydroxyanthracene, vinylnaphthalene, biphenyl, bisphenol, trisphenol, dicyclopentadiene, tetrahydroindene, 4-vinylcyclohexene, norbornene, 5-vinylnorbornene-2-ene, α-pinene, β-pinene, phenolic novolac resins such as limonene, polyhydroxystyrene, polystyrene, polyvinylnaphthalene, polyvinylanthracene, polyvinylcarbazole, polyindene, polyvinylnaphthalene, polynorbornene, polycyclodecene, polytetracyclododecene, polytricyclo[2.2.1.0(2,6)]heptane (poly-nortricyclene), poly(meth)acrylates, and copolymers thereof. Furthermore, naphthol dicyclopentadiene copolymers described in Japanese Patent Application Laid-Open No. 2004-205685, fluorene bisphenol novolac resins described in Japanese Patent Application Laid-Open No. 2005-128509, ethylene naphthalene copolymers described in Japanese Patent Application Laid-Open No. 2005-250434, fullerenes having a phenol group described in Japanese Patent Application Laid-Open No. 2006-227391, bisphenol compounds and novolac resins thereof described in Japanese Patent Application Laid-Open No. 2006-293298, novolac resins of adamantane phenol compounds described in Japanese Patent Application Laid-Open No. 2006-285095, bisnaphthol compounds and novolac resins thereof described in Japanese Patent Application Laid-Open No. 2010-122656, fullerene resin compounds described in Japanese Patent Application Laid-Open No. 2008-158002, and the like may also be blended. The amount of the modifier blended is preferably 0 to 1,000 parts by mass, more preferably 0 to 500 parts by mass, relative to 100 parts by mass of the polymer having a partial structure represented by the general formula (1) or (2), or having a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3) of the present invention.

[0186] [Organic solvents]

[0187] The organic solvent that can be used in the coating type organic film forming composition of the present invention is not particularly limited as long as it can dissolve the polymer having the partial structure represented by the general formula (1) or (2), or the partial structure represented by the general formula (1) or (2) and the partial structure represented by the general formula (3), any components, such as the acid generator, crosslinking agent, other additives, etc. described below. Specifically, a solvent having a boiling point of less than 160° C. such as the solvents described in paragraphs (0091) to (0092) of Japanese Patent Application Laid-Open No. 2007-199653 can be used. Among them, propylene glycol monomethyl ether acetate, propylene glycol monomethyl ether, 2-heptanone, cyclopentanone, cyclohexanone, and a mixture of two or more thereof can be preferably used.

[0188] Such a composition can be applied by spin coating, and since it contains the polymer having the partial structure represented by the general formula (1) or (2) or the partial structure represented by the general formula (1) or (2) and the partial structure represented by the general formula (3) of the present invention as described above, it can be a coating type organic film forming composition having good pattern bending resistance and good dry etching resistance, and can suppress the occurrence of defects. Moreover, such a composition can form an organic film having both heat resistance and high filling / planarization characteristics.

[0189] In addition, in the coating type organic film forming composition of the present invention, a solvent having a boiling point of 160°C or higher (a mixture of one or more organic solvents having a boiling point of less than 160°C and one or more organic solvents having a boiling point of 160°C or higher) may be used as an organic solvent. The high boiling point organic solvent is not particularly limited as long as it can dissolve a polymer having a partial structure represented by the general formula (1) or (2) or a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3). Examples thereof include hydrocarbons, alcohols, ketones, esters, ethers, chlorine-based solvents, and the like. Specific examples thereof include 1,2,4-trimethylbenzene, 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-octanol, 2-ethylhexanol, 1-nonanol, 1-decanol, 1-undecanol, ethylene glycol, 1,2-propylene glycol, 1,3-butanediol, Alcohol, 2,4-pentanediol, 2-methyl-2,4-pentanediol, 2,5-hexanediol, 2,4-heptanediol, 2-ethyl-1,3-hexanediol, diethylene glycol, dipropylene glycol, triethylene glycol, tripropylene glycol, glycerol, n-nonyl acetate, ethylene glycol, diethylene glycol dimethyl ether, monohexyl ether, ethylene glycol mono-2-ethylhexyl ether, ethylene glycol monophenyl ether, ethylene glycol monobenzyl ether, diethylene glycol monoethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol mono-n-butyl ether, diethylene glycol monoisobutyl ether, diethylene glycol monohexyl ether, diethylene glycol monophenyl ether, diethylene glycol monobenzyl ether, diethylene glycol Ethylene glycol diethyl ether, diethylene glycol dibutyl ether, diethylene glycol butyl methyl ether, triethylene glycol dimethyl ether, triethylene glycol monomethyl ether, triethylene glycol n-butyl ether, triethylene glycol butyl methyl ether, triethylene glycol diacetate, tetraethylene glycol dimethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol mono-n-propyl ether, dipropylene glycol mono-n-butyl ether, tripropylene glycol dimethyl ether, tripropylene glycol monomethyl ether, tripropylene glycol mono-n-propyl ether, tripropylene glycol mono-n-butyl ether, propylene glycol monoethyl ether acetate, ethyl 3-ethoxypropionate, ethylene glycol monoethyl ether acetate, ethylene glycol monobutyl ether acetate, diethylene glycol monomethyl ether acetate, diethylene Glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, triacetin, propylene glycol diacetate, dipropylene glycol monomethyl ether acetate, dipropylene glycol methyl n-propyl ether, dipropylene glycol methyl ether acetate, 1,4-butanediol diacetate, 1,3-butanediol diacetate, 1,6-hexanediol diacetate, triethylene glycol diacetate, γ-butyrolactone, dihexyl malonate, diethyl succinate, dipropyl succinate, dibutyl succinate, dihexyl succinate, dimethyl adipate, diethyl adipate, dibutyl adipate, etc., which can be used alone or in combination.

[0190] The boiling point of the high boiling point solvent can be appropriately selected according to the temperature at which the coating type organic film forming composition is subjected to heat treatment, and the boiling point of the added high boiling point solvent is preferably 160°C to 300°C. If the boiling point is 160°C or higher, there is no risk of excessively rapid volatilization during baking (heat treatment) due to too low a boiling point, and sufficient thermal fluidity can be obtained. In addition, if the boiling point is 300°C or lower, there is no risk of excessively high boiling point solvent remaining in the organic film after baking without volatilization, and there is no risk of adversely affecting the film properties such as etching resistance.

[0191] When the high boiling point solvent is used, the amount of the high boiling point solvent blended is preferably 1 to 50 parts by mass relative to 100 parts by mass of the solvent having a boiling point of less than 160° C. If such an amount is blended, there is no risk of failure to impart sufficient thermal fluidity during baking or of remaining in the organic film, resulting in deterioration of film properties such as etching resistance.

[0192] If such a coating type organic film forming composition is used, by adding a high boiling point solvent to a polymer having a partial structure represented by the general formula (1) or (2), or having a partial structure represented by the general formula (1) or (2) and a partial structure represented by the general formula (3) to impart thermal fluidity, it will become a coating type organic film forming composition having a high degree of filling / planarization properties.

[0193] [Other additives]

[0194] In order to further promote the curing reaction, an acid generator may be added to the coating type organic film forming composition of the present invention. Acid generators may generate acid by thermal decomposition or by light irradiation, and both may be added. Specifically, materials described in paragraphs (0061) to (0085) of Japanese Patent Publication No. 2007-199653 may be added, but the present invention is not limited thereto.

[0195] The acid generator may be used alone or in combination of two or more. The amount of the acid generator added is preferably 0.05 to 50 parts by mass, more preferably 0.1 to 10 parts by mass, relative to 100 parts by mass of the polymer having the partial structure represented by the general formula (1) or (2), or having the partial structure represented by the general formula (1) or (2) and the partial structure represented by the general formula (3).

[0196] The coating type organic film-forming composition of the present invention may contain a surfactant to improve coating properties in spin coating. For example, the surfactant described in (0142) to (0147) of JP-A-2009-269953 may be used.

[0197] In addition, in the coating type organic film forming composition of the present invention, a crosslinking agent may be added in order to improve the curability and further inhibit the cross-mixing with the upper film. The crosslinking agent is not particularly limited, and various well-known crosslinking agents can be widely used. As an example, melamine crosslinking agents, glycoluril crosslinking agents, benzoguanamine crosslinking agents, urea crosslinking agents, β-hydroxyalkylamide crosslinking agents, isocyanurate crosslinking agents, aziridine crosslinking agents, oxazoline crosslinking agents, epoxy crosslinking agents, and tertiary alcohol crosslinking agents can be illustrated.

[0198] As melamine-based crosslinking agents, specifically, hexamethoxymethylated melamine, hexabutoxymethylated melamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As glycoluril-based crosslinking agents, specifically, tetramethoxymethylated glycoluril, tetrabutoxymethylated glycoluril, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As benzoguanamine-based crosslinking agents, specifically, tetramethoxymethylated benzoguanamine, tetrabutoxymethylated benzoguanamine, their alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As urea-based crosslinking agents, specifically, dimethoxymethylated dimethoxyethylene urea, its alkoxy and / or hydroxyl substitutions, and their partial self-condensation products can be exemplified. As β-hydroxyalkylamide-based crosslinking agents, specifically, N,N,N',N'-tetrakis(2-hydroxyethyl)adipamide can be exemplified. Specific examples of isocyanurate crosslinking agents include triglycidyl isocyanurate and triallyl isocyanurate. Specific examples of aziridine crosslinking agents include 4,4'-bis(ethyleneiminocarbonylamino)diphenylmethane and 2,2-bishydroxymethylbutanol-tris[3-(1-aziridinyl)propionate]. Specific examples of the oxazoline crosslinking agent include 2,2'-isopropylidenebis(4-benzyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-isopropylidenebis(4-phenyl-2-oxazoline), 2,2'-methylenebis-4,5-diphenyl-2-oxazoline, 2,2'-methylenebis-4-phenyl-2-oxazoline, 2,2'-methylenebis-4-tert-butyl-2-oxazoline, 2,2'-bis(2-oxazoline), 1,3-phenylenebis(2-oxazoline), 1,4-phenylenebis(2-oxazoline), and 2-isopropenyloxazoline copolymers. Specific examples of the epoxy crosslinking agent include diglycidyl ether, ethylene glycol diglycidyl ether, 1,4-butanediol diglycidyl ether, 1,4-cyclohexanedimethanol diglycidyl ether, poly(glycidyl methacrylate), trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, and pentaerythritol tetraglycidyl ether.

[0199] As the tertiary alcohol cross-linking agent, specifically, the compound of the following formula can be exemplified, but it is not limited thereto.

[0200] [Chemistry 21]

[0201]

[0202] In addition, in order to further improve the planarization / burying characteristics, a plasticizer may be added to the coating type organic film forming composition of the present invention. The plasticizer is not particularly limited, and plasticizers of various known systems can be widely used. As an example, low molecular weight compounds such as phthalates, adipic acid esters, phosphates, trimellitic acid esters, and citrates, polyethers, polyesters, and polymers such as polyacetal polymers described in Japanese Patent Application Laid-Open No. 2013-253227 can be illustrated.

[0203] In the coating type organic film forming composition of the present invention, as an additive for imparting the filling / planarizing property similarly to the plasticizer, for example, a liquid additive having a polyethylene glycol or polypropylene glycol structure, or a thermally decomposable polymer having a weight loss rate of 40% by mass or more at 30° C. to 250° C. and a weight average molecular weight of 300 to 200,000 can be preferably used. The thermally decomposable polymer preferably contains a repeating unit having an acetal structure represented by the following general formula (DP1) or (DP1a).

[0204] [Chemistry 22]

[0205]

[0206] In the formula, R6 is a hydrogen atom or an optionally substituted saturated or unsaturated monovalent organic group having 1 to 30 carbon atoms. Y1 is a saturated or unsaturated divalent organic group having 2 to 30 carbon atoms.

[0207] [Chemistry 23]

[0208]

[0209] In the formula, R 6a Y is an alkyl group having 1 to 4 carbon atoms. a It is a saturated or unsaturated divalent hydrocarbon group having 4 to 10 carbon atoms, and may have an ether bond. n represents the average number of repeating units, and is 3 to 500.

[0210] The coating type organic film forming composition of the present invention can be used alone or in combination of two or more. The coating type organic film forming composition can be used as a material for forming an organic film provided under a resist underlayer film or as a planarizing material for semiconductor device manufacturing.

[0211] In addition, the coating-type organic film forming composition of the present invention is extremely useful as an organic film material for multi-layer resist processing such as a two-layer resist processing, a three-layer resist processing using a silicon-containing underlayer film, and a four-layer resist processing using a silicon-containing inorganic hard mask and an organic anti-reflective film.

[0212] <Organic film formation method>

[0213] By using the coating type organic film-forming composition of the present invention, an organic film that functions as a resist underlayer film of a multilayer resist film used in photolithography or a planarizing film for semiconductor manufacturing can be formed.

[0214] In the organic film forming method of this example, the coating type organic film forming composition of the present invention is applied to the processed substrate by spin coating or the like. By using the spin coating method or the like, good filling characteristics can be obtained. After spin coating, the solvent is evaporated, and baking (heat treatment) is performed to prevent mixing with the resist upper film and the resist lower film and to promote the cross-linking reaction. The baking is preferably carried out in the range of 100°C to 600°C and 10 to 600 seconds, and more preferably in the range of 200°C to 500°C and 10 to 300 seconds. Considering the influence on device damage and wafer deformation, the upper limit of the heating temperature in the wafer process of photolithography is preferably below 600°C, and more preferably below 500°C.

[0215] Furthermore, an organic film can also be formed by coating the coating type organic film forming composition of the present invention on a substrate to be processed by the same spin coating method as described above, and then calcining the coating type organic film forming composition in an environment with an oxygen concentration of 0.1% to 21% to harden it.

[0216] By calcining the coating type organic film forming composition of the present invention in such an oxygen environment, a fully hardened organic film can be obtained. The environment during baking can be in air, and in order to reduce oxygen, inert gases such as N2, Ar, and He are enclosed, and it is preferred to prevent the oxidation of the organic film. In order to prevent oxidation, the oxygen concentration needs to be controlled, preferably below 1000ppm, more preferably below 100ppm. If the oxidation of the organic film during baking is prevented, there will be no absorption increase, or the etching resistance will be reduced, so it is preferred.

[0217] Such an organic film forming method, due to its excellent filling / planarization characteristics, can obtain a flat organic film regardless of the unevenness of the processed substrate. Therefore, it is extremely useful in forming a flat organic film on a processed substrate with a structure having a height of more than 30nm or a height difference.

[0218] The thickness of the organic film such as the resist underlayer film or the planarization film for manufacturing a semiconductor device can be appropriately selected, and is preferably 30 to 20,000 nm, more preferably 50 to 15,000 nm.

[0219] <Pattern Formation Method>

[0220] In the present invention, with respect to a pattern forming method using such a coating type organic film forming composition and utilizing a three-layer resist process, a pattern forming method is provided, which is a method for forming a pattern on a processed substrate, and at least comprises the following steps: forming an organic film on a processed object using the organic film forming composition of the present invention; forming a silicon-containing resist underlayer film on the organic film using a silicon-containing resist underlayer film material; forming a resist upper layer film on the silicon-containing resist underlayer film using a photoresist composition; forming a circuit pattern on the resist upper layer film; using the aforementioned resist upper layer film on which the pattern has been formed as a mask, etching the aforementioned silicon-containing resist underlayer film, and transferring the pattern to the silicon-containing resist underlayer film; using the aforementioned silicon-containing resist underlayer film to which the pattern has been transferred as a mask, etching the aforementioned organic film, and transferring the pattern to the organic film; and using the aforementioned organic film to which the pattern has been transferred as a mask, etching the aforementioned processed object, and forming a pattern on the processed object.

[0221] The silicon-containing resist underlayer film in the above-mentioned three-layer resist treatment shows etching resistance to oxygen or hydrogen. Therefore, in the above-mentioned three-layer resist treatment, it is preferred to use an etching gas mainly composed of oxygen or hydrogen to perform dry etching of the organic film using the silicon-containing resist underlayer film as a mask.

[0222] The silicon-containing resist lower film in the above three-layer resist treatment can also be preferably a polysiloxane-based lower film. By making the silicon-containing resist lower film have an anti-reflection effect, reflection can be suppressed. Especially for 193nm exposure, if a material containing a large number of aromatic groups and having a high etching selectivity with the substrate is used as an organic film, the k value increases and the substrate reflection becomes high, but by making the silicon-containing resist lower film have an absorption that can become an appropriate k value, reflection can be suppressed and the substrate reflection can be reduced to less than 0.5%. As a silicon-containing resist lower film with an anti-reflection effect, it is ideal to use an anthracene-suspended film for 248nm and 157nm exposure, and it is ideal to use a polysiloxane-containing resist lower film that has a light-absorbing group containing a phenyl group or a silicon-silicon bond and can be cross-linked by acid or heat for 193nm exposure.

[0223] An organic anti-reflective film (BARC) can also be formed on the aforementioned silicon-containing resist lower film. In this case, a pattern can be formed on the aforementioned workpiece by the following steps: an organic film is formed on the workpiece using the coating type organic film forming composition of the present invention; a silicon-containing resist lower film is formed on the organic film using a silicon-containing resist lower film material; an organic anti-reflective film (BARC) is formed on the silicon-containing resist lower film; a photoresist composition is used on the organic anti-reflective film to form a resist upper film, so as to form a 4-layer film structure. structure; forming a circuit pattern on the resist upper film; using the resist upper film with the pattern formed as a mask, etching the organic anti-reflective film and the silicon-containing resist lower film, transferring the pattern to the organic anti-reflective film and the silicon-containing resist lower film; using the silicon-containing resist lower film with the pattern transferred as a mask, etching the organic film, transferring the pattern to the organic film; and using the organic film with the pattern transferred as a mask, etching the object to be processed, forming a pattern on the object to be processed.

[0224] Furthermore, an inorganic hard mask may be formed as an anti-etching lower film. In this case, a pattern may be formed on the aforementioned workpiece by the following steps: an organic film is formed on the workpiece using the coating-type organic film forming composition of the present invention; an inorganic hard mask selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film is formed on the organic film; a photoresist composition is used on the inorganic hard mask to form an anti-etching upper film; a circuit pattern is formed on the anti-etching upper film; the aforementioned anti-etching upper film with the pattern formed is used as a mask to etch the aforementioned inorganic hard mask to transfer the pattern to the inorganic hard mask; the aforementioned inorganic hard mask with the pattern transferred thereto is used as a mask to etch the aforementioned organic film to transfer the pattern to the organic film; and the aforementioned workpiece is etched using the organic film with the pattern transferred thereto as a mask to form a pattern on the workpiece.

[0225] As described above, when an inorganic hard mask is formed on an organic film, for example, a silicon oxide film, a silicon nitride film, and a silicon oxide nitride film (SiON film) can be formed by a CVD method, an ALD method, or the like. The method for forming a silicon nitride film is described, for example, in Japanese Patent Application Publication No. 2002-334869 and International Publication No. 2004 / 066377. The thickness of the inorganic hard mask is preferably 5 to 200 nm, more preferably 10 to 100 nm. In addition, it is best to use a SiON film that has a high effect as an anti-reflective film as the inorganic hard mask. The substrate temperature when forming the SiON film is 300 to 500°C, so the lower film needs to withstand a temperature of 300 to 500°C. The organic film forming composition used in the present invention has high heat resistance and can withstand a high temperature of 300 to 500°C, so it can be a combination of an inorganic hard mask formed by a CVD method or an ALD method and an organic film formed by a spin coating method.

[0226] In addition, a four-layer resist process using BARC is also ideal. In this case, a pattern can be formed on the aforementioned workpiece through the following steps: an organic film is formed on the workpiece using the coating-type organic film forming composition of the present invention; an inorganic hard mask selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film is formed on the organic film; an organic anti-reflective film is formed on the inorganic hard mask; a photoresist composition is used on the organic anti-reflective film to form a resist upper film to form a four-layer film structure; a circuit pattern is formed on the resist upper film; the aforementioned patterned resist upper film is used as a mask to etch the aforementioned organic anti-reflective film and the aforementioned inorganic hard mask, and the pattern is transferred to the organic anti-reflective film and the inorganic hard mask; the aforementioned patterned inorganic hard mask is used as a mask to etch the aforementioned organic film, and the pattern is transferred to the organic film; and the aforementioned patterned organic film is used as a mask to etch the aforementioned workpiece to form a pattern on the workpiece.

[0227] As described above, a photoresist film can be formed on an inorganic hard mask as a resist upper film, and a BARC can be formed on the inorganic hard mask by spin coating, and then a photoresist film can be formed thereon. In particular, when a SiON film is used as an inorganic hard mask, the two-layer anti-reflection film of the SiON film and the BARC can suppress reflection even in immersion exposure with a high NA exceeding 1.0. Another advantage of forming a BARC is that it has the effect of reducing the tailing of the photoresist pattern directly above the SiON film.

[0228] The resist upper film in the above-mentioned 3-layer and 4-layer resist treatment can be positive or negative, and can use the same photoresist composition as commonly used. It is preferred that the photoresist composition be spin-coated and then pre-baked at 60 to 180°C for 10 to 300 seconds. Thereafter, exposure is performed according to the usual method, and post-exposure baking (PEB) and development are further performed to obtain a resist pattern. In addition, the thickness of the resist upper film is not particularly limited, and is preferably 30 to 500 nm, and particularly preferably 50 to 400 nm.

[0229] Examples of exposure light include high energy rays having a wavelength of 300 nm or less, and specifically, excimer lasers of 248 nm, 193 nm, and 157 nm, and soft X-rays, electron beams, and X-rays of 3 to 20 nm.

[0230] In the pattern forming method of the present invention, as a method for forming a circuit pattern on the resist upper layer film, optical lithography using light with a wavelength of 10 nm to 300 nm, direct writing using an electron beam, nanoimprinting, or a combination thereof is preferably used.

[0231] In the pattern forming method of the present invention, it is preferable to use alkali development or development using an organic solvent as a development method.

[0232] Then, the obtained resist pattern is used as a mask for etching. The etching of the silicon-containing resist lower film and the inorganic hard mask in the three-layer or four-layer resist process is performed using a fluorocarbon gas and the upper resist pattern as a mask. In this way, the silicon-containing resist lower film pattern and the inorganic hard mask pattern are formed.

[0233] Then, the organic film is etched using the obtained silicon-containing resist underlayer film pattern and inorganic hard mask pattern as masks.

[0234] The etching of the processed substrate and other processed objects can also be performed using conventional methods. For example, if the processed substrate is SiO2, SiN, or a silicon dioxide-based low-dielectric insulating film, etching is performed mainly using a flon-based gas. If it is p-Si, Al, or W, etching is performed mainly using a chlorine-based or bromine-based gas. When etching the substrate using a flon-based gas, the silicon-containing resist lower film pattern in the 3-layer or 4-layer resist process will be stripped off while the substrate is being processed. When etching the substrate using a chlorine-based or bromine-based gas, the stripping of the silicon-containing resist lower film pattern requires additional dry etching stripping using a flon-based gas after the substrate is processed.

[0235] As described above, the organic film obtained by using the coating type organic film-forming composition of the present invention has the characteristic of being excellent in etching resistance when etching these substrates to be processed.

[0236] In the pattern forming method of the present invention, the object to be processed is preferably a semiconductor device substrate, a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film or a metal oxide nitride film.

[0237] In addition, the aforementioned object to be processed preferably includes silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, molybdenum or an alloy thereof.

[0238] In addition, the substrate to be processed is not particularly limited, and substrates such as Si, α-Si, p-Si, SiO2, SiN, SiON, W, TiN, Al, etc., and a substrate on which a processed layer is formed, etc. can be used. The processed layer can be various Low-k films such as Si, SiO2, SiON, SiN, p-Si, α-Si, W, W-Si, Al, Cu, Al-Si, and barrier films thereof, and can generally be formed to a thickness of preferably 50 to 10,000 nm, more preferably 100 to 5,000 nm. In addition, when the processed layer is formed, the substrate and the processed layer can be made of different materials.

[0239] The substrate to be processed preferably has a structure or a height difference of 30 nm or more. The organic film formed on such a substrate using the coating type organic film forming composition of the present invention can exhibit excellent filling characteristics and excellent planarization characteristics.

[0240] For an example of 3-layer resist processing, using Figure 1 The specific display is as follows.

[0241] When the 3-layer resist is processed, Figure 1 As shown in (A), an organic film 3 is formed on a processing layer 2 stacked on a substrate 1 using the organic film-forming composition of the present invention, and then a silicon-containing resist underlayer film 4 is formed, and a resist upperlayer film 5 is formed thereon.

[0242] Then, if Figure 1 As shown in (B), the used portion 6 of the resist upper film 5 is exposed, and PEB and development are performed to form a resist upper film pattern 5a ( Figure 1 (C)). The obtained resist upper film pattern 5a is used as a mask, and the silicon-containing resist lower film 4 is etched using CF-based gas to form a silicon-containing resist lower film pattern 4a ( Figure 1 (D)). After removing the resist upper film pattern 5a, the obtained silicon-containing resist lower film pattern 4a is used as a mask to perform oxygen plasma etching on the organic film 3 to form an organic film pattern 3a ( Figure 1 (E)). After further removing the silicon-containing resist lower film pattern 4a, the processed layer 2 is etched using the organic film pattern 3a as a mask to form a pattern 2a on the processed layer 2 ( Figure 1 (F)).

[0243] When an inorganic hard mask is used, the inorganic hard mask is used instead of the silicon-containing resist lower film 4. When forming BARC, a BARC layer is provided between the silicon-containing resist lower film 4 or the inorganic hard mask and the resist upper film 5. BARC etching may be performed continuously before etching the silicon-containing resist lower film 4, or etching of the silicon-containing resist lower film 4 may be performed after etching of BARC alone, and then etching of the silicon-containing resist lower film 4 may be performed by changing the etching device.

[0244] As described above, according to the pattern forming method of the present invention, a fine pattern can be formed on a workpiece with high precision in a multilayer resist process.

[0245] Example

[0246] Hereinafter, the present invention will be described in more detail by citing synthesis example, comparative synthesis example, embodiment and comparative example, but the present invention is not limited thereto. In addition, with regard to molecular weight and dispersity, the weight average molecular weight (Mw) and number average molecular weight (Mn) of polystyrene conversion are obtained by gel permeation chromatography (GPC) using tetrahydrofuran as eluent, and dispersity (Mw / Mn) is obtained.

[0247] The synthesis of polymers (A1) to (A17) contained in the organic film-forming composition described below uses the following fluorenols (B1) to (B10) and the following aromatic-containing compounds (C1) to (C5).

[0248] [Chemistry 24]

[0249] Fluorenols

[0250]

[0251] [Chemistry 25]

[0252] Aromatic compounds

[0253]

[0254] When a plurality of fluorenols are used to synthesize a polymer, the ratio of the fluorenols added is described using m and l in the following formula.

[0255] [Chemistry 26]

[0256]

[0257] Synthesis Example Synthesis of Etching Resistant Organic Compound

[0258] [Synthesis Example 1] Synthesis of polymer (A1)

[0259] [Chemistry 27]

[0260]

[0261] Mix 54.5 g of fluorenol (B1) and 200 g of 1,2-dichloroethane, and heat to 50°C. Slowly drop 20.3 g of methanesulfonic acid, heat and stir at 70°C for 6 hours. After cooling to room temperature, add 650 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 600 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 60.7 g of polymer (A1).

[0262] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0263] (A1): Mw=2700, Mw / Mn=1.39

[0264] [Synthesis Example 2] Synthesis of polymer (A2)

[0265] [Chemistry 28]

[0266]

[0267] Mix 61.7 g of fluorenol (B2) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 600 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 56.7 g of polymer (A2).

[0268] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0269] (A2): Mw=2780, Mw / Mn=1.35

[0270] [Synthesis Example 3] Synthesis of polymer (A3)

[0271] [Chemistry 29]

[0272]

[0273] Mix 61.7 g of fluorenol (B3) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 600 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 57.5 g of polymer (A3).

[0274] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0275] (A3): Mw=2810, Mw / Mn=1.36

[0276] [Synthesis Example 4] Synthesis of polymer (A4)

[0277] [Chemistry 30]

[0278]

[0279] Mix 71.7 g of fluorenol (B4) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 680 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 68.1 g of polymer (A4).

[0280] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0281] (A4): Mw=2900, Mw / Mn=1.38

[0282] [Synthesis Example 5] Synthesis of polymer (A5)

[0283] [Chemistry 31]

[0284]

[0285] Mix 67.7 g of fluorenol (B5) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 650 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 64.0 g of polymer (A5).

[0286] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0287] (A5): Mw=2950, ​​Mw / Mn=1.40

[0288] [Synthesis Example 6] Synthesis of polymer (A6)

[0289] [Chemistry 32]

[0290]

[0291] Mix 71.7 g of fluorenol (B6) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 600 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 68.0 g of polymer (A6).

[0292] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0293] (A6): Mw=2890, Mw / Mn=1.39

[0294] [Synthesis Example 7] Synthesis of polymer (A7)

[0295] [Chemistry 33]

[0296]

[0297] Mix 71.7 g of fluorenol (B7) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 680 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 68.0 g of polymer (A7).

[0298] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0299] (A7): Mw=2870, Mw / Mn=1.38

[0300] [Synthesis Example 8] Synthesis of polymer (A8)

[0301] [Chemistry 34]

[0302]

[0303] Mix 76.5 g of fluorenol (B8) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 700 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 72.8 g of polymer (A8).

[0304] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0305] (A8): Mw=2920, Mw / Mn=1.41

[0306] [Synthesis Example 9] Synthesis of polymer (A9)

[0307] [Chemistry 35]

[0308]

[0309] Mix 71.7 g of fluorenol (B9) and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. Add 200 g of THF to the residue to make a uniform solution, and then crystallize it in 680 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 68.1 g of polymer (A9).

[0310] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0311] (A9): Mw=2890, Mw / Mn=1.38

[0312] [Synthesis Example 10] Synthesis of polymer (A10)

[0313] [Chemistry 36]

[0314]

[0315] Mix 9.2 g of fluorenol (B3), 0.5 g of an aromatic compound (C1), and 50 g of dichloromethane. Slowly add 3.2 g of methanesulfonic acid dropwise and heat to reflux for 17 hours. After cooling to room temperature, add 100 g of methyl isobutyl ketone, wash 6 times with 50 g of pure water, and reduce the pressure to dry the organic layer. After adding 20 g of THF to the residue to make a uniform solution, crystallize it in 90 g of methanol. Filter and separate the precipitated crystals, wash twice with 20 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 8.6 g of polymer (A10).

[0316] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0317] (A10): Mw=1520, Mw / Mn=1.25

[0318] [Synthesis Example 11] Synthesis of polymer (A11)

[0319] [Chemistry 37]

[0320]

[0321] Mix 9.2 g of fluorenol (B3), 0.5 g of an aromatic compound (C2) and 50 g of dichloromethane. Slowly add 3.2 g of methanesulfonic acid dropwise and heat to reflux for 17 hours. After cooling to room temperature, add 100 g of methyl isobutyl ketone, wash 6 times with 50 g of pure water, and reduce the pressure to dry the organic layer. Add 20 g of THF to the residue to make a uniform solution, and then crystallize it in 90 g of methanol. Filter and separate the precipitated crystals, wash twice with 20 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 9.0 g of polymer (A11).

[0322] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0323] (A11): Mw=1630, Mw / Mn=1.22

[0324] [Synthesis Example 12] Synthesis of polymer (A12)

[0325] [Chemistry 38]

[0326]

[0327] Mix 61.7 g of fluorenol (B3), 4.2 g of an aromatic compound (C3) and 160 g of dichloromethane. Slowly add 21.6 g of methanesulfonic acid dropwise and heat to reflux for 18 hours. After cooling to room temperature, add 300 g of methyl isobutyl ketone, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 650 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 62.2 g of polymer (A12).

[0328] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0329] (A12): Mw=1420, Mw / Mn=1.19

[0330] [Synthesis Example 13] Synthesis of polymer (A13)

[0331] [Chemistry 39]

[0332]

[0333] Mix 61.7 g of fluorenol (B3), 11.3 g of an aromatic compound (C4) and 160 g of dichloromethane. Slowly add 21.6 g of methanesulfonic acid dropwise and heat to reflux for 18 hours. After cooling to room temperature, add 300 g of methyl isobutyl ketone, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 700 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 69.3 g of polymer (A13).

[0334] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0335] (A13): Mw=2020, Mw / Mn=1.24

[0336] [Synthesis Example 14] Synthesis of polymer (A14)

[0337] [Chemistry 40]

[0338]

[0339] Mix 61.7 g of fluorenol (B3) with 19.2 g of an aromatic compound (C5) and 160 g of dichloromethane. Slowly add 21.6 g of methanesulfonic acid dropwise and heat to reflux for 18 hours. After cooling to room temperature, add 300 g of methyl isobutyl ketone, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 800 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 77.2 g of polymer (A14).

[0340] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0341] (A14): Mw=2200, Mw / Mn=1.27

[0342] [Synthesis Example 15] Synthesis of polymer (A15)

[0343] [Chemistry 41]

[0344]

[0345] Mix 43.2 g of fluorenol (B3), 10.9 g of fluorenol (B10), and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 150 g of THF to the residue to make a uniform solution, crystallize it in 500 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 52.5 g of polymer (A15).

[0346] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0347] (A15): Mw=2890, Mw / Mn=1.60

[0348] [Synthesis Example 16] Synthesis of polymer (A16)

[0349] [Chemistry 42]

[0350]

[0351] Mix 38.4 g of fluorenol (B3), 2.6 g of an aromatic compound (C3), 10.9 g of fluorenol (B10), and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat under reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 150 g of THF to the residue to make a uniform solution, crystallize it in 500 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 50.5 g of polymer (A16).

[0352] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0353] (A16): Mw=1520, Mw / Mn=1.24

[0354] [Synthesis Example 17] Synthesis of polymer (A17)

[0355] [Chemistry 43]

[0356]

[0357] Mix 61.7 g of fluorenol (B3), 0.36 g of water and 160 g of dichloromethane. Slowly add 19.2 g of methanesulfonic acid dropwise and heat to reflux for 8 hours. After cooling to room temperature, add 250 g of toluene, wash 6 times with 100 g of pure water, and reduce the pressure to dry the organic layer. After adding 200 g of THF to the residue to make a uniform solution, crystallize it in 600 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 57.5 g of polymer (A17).

[0358] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0359] (A17): Mw=1850, Mw / Mn=1.26

[0360] Synthesis Example Synthesis of Tertiary Alcohol Crosslinking Agent

[0361] [Synthesis Example 18] Synthesis of Compound (A18)

[0362] [Chemistry 44]

[0363]

[0364] Under N2 environment, add 500 mL of 2.67 M hexane solution of n-butyl lithium to a mixture of 219 g of bis(4-bromophenyl) ether and 1000 mL of tert-butyl methyl ether cooled to -20°C, and stir at -20°C for 20 minutes. Add 229 g of 9-fluorenone, slowly warm to room temperature, and stir at room temperature for 4 hours. Add water to stop the reaction. After washing with water and concentrating under reduced pressure, add hexane, filter the generated solid, wash with hexane, and dry under reduced pressure to obtain 293 g of diol (A18).

[0365] IR (D-ATR): ν=3440, 3066, 3039, 1595, 1496, 1448, 1212, 1164, 1038, 1032, 923, 822, 767, 751, 732cm -1 .

[0366] 1 H-NMR (600MHz, in DMSO-d6): δ=6.29(2H,-OH,s), 6.83(4H,d), 7.20-7.25(12H,m), 7.33-7.36(4H,m), 7.79(4H,d)ppm.

[0367] Comparative Synthesis Example Synthesis of Curable Organic Compounds

[0368] [Comparative Synthesis Example 1] Synthesis of Polymer (R1)

[0369] [Chemistry 45]

[0370]

[0371] Mix 12.8 g of naphthalene and 18.0 g of 9-fluorenone, raise the temperature to 230°C and react for 8 hours. After the reaction starts, add 0.25 mL of methanesulfonic acid to the reaction solution 8 times every hour. After cooling to room temperature, add 40 g of toluene and 20 g of anisole, wash with pure water 6 times, and reduce the pressure to dry the organic layer. After adding 100 g of THF (tetrahydrofuran) to the residue to make a uniform solution, crystallize it in 300 g of methanol. Filter and separate the precipitated crystals, wash twice with 200 g of methanol and recover them. The recovered crystals are vacuum dried at 70°C to obtain 20.0 g of polymer (R1).

[0372] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0373] (R1): Mw=2130, Mw / Mn=2.61

[0374] [Comparative Synthesis Example 2] Synthesis of Compound (R2)

[0375] [Chemistry 46]

[0376]

[0377] 7.7 g of aromatic compound (C5), 3.0 g of potassium carbonate, and 40 g of N,N-dimethylformamide were mixed and heated to 55°C. 3.3 g of 80% toluene solution of propyne bromide was slowly added dropwise, and the mixture was heated and stirred at 55°C for 14 hours. After cooling to room temperature, 150 g of toluene was added, and the mixture was washed with water and concentrated under reduced pressure to obtain 8.4 g of propargyl body (R2).

[0378] The weight average molecular weight (Mw) and the degree of dispersion (Mw / Mn) were determined by GPC. The results are as follows.

[0379] (R2): Mw=966, Mw / Mn=1.09

[0380] Preparation of organic film-forming compositions (UDL-1 to 20, comparative UDL 1 to 3)

[0381] The polymers (A1) to (A17), any one of the polymers (R1) and the compound (R2), and (A18) or (XL1) as a crosslinking agent were dissolved in a solvent containing 0.05% by mass of an acid generator (AG1) and 0.1% by mass of a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) at the ratios shown in Tables 1 and 2, and filtered using a 0.1 μm fluororesin filter to prepare coating-type organic film-forming compositions (materials) (UDL-1 to 20, comparative UDL-1 to 3). The solvents used were propylene glycol monomethyl ether acetate (PGMEA), cyclohexanone (CyHO) and / or 1,2,4-trimethylbenzene (TMB) at the ratios shown in Tables 1 and 2. UDL-19, comparative UDL-1 and comparative UDL-3 did not contain a crosslinking agent.

[0382] [Table 1]

[0383]

[0384] [Table 2]

[0385]

[0386] The acid generator (AG1) and the cross-linking agent (XL1) are shown below.

[0387] [Chemistry 47]

[0388]

[0389] Example 1 Solvent Resistance Measurement (Examples 1-1 to 1-20, Comparative Examples 1-1 to 1-3)

[0390] The organic film-forming composition (UDL-1 to 20, comparative UDL-1 to 3) prepared above was applied on a silicon substrate, and after calcination at 350°C in the atmosphere for 60 seconds, the film thickness was measured. Then, PGMEA solvent was dispensed on the coated film, left for 30 seconds and spin-dried, and baked at 100°C for 60 seconds to evaporate PGMEA (PGMEA treatment). After treatment, the film thickness was measured. The difference in film thickness before and after PGMEA treatment was calculated as the ratio of the film thickness b after treatment to the film thickness a before treatment (residual film rate). These results are shown in Table 3.

[0391] [Table 3]

[0392]

[0393] As shown in Table 3, the organic film-forming composition of the present invention (Examples 1-1 to 1-20) has a residual film rate of 99% or more after PGMEA treatment, and a crosslinking reaction occurs due to heat treatment, showing sufficient solvent resistance. In particular, from the comparison between Example 1-19 and Example 1-20, it can be seen that the organic film-forming composition of the present invention can still show sufficient solvent resistance even if it does not contain a crosslinking agent. On the other hand, from the comparison between Comparative Example 1-1 and Comparative Example 1-2, it can be seen that the comparative UDL-1 using the polymer (R1) does not show solvent resistance alone because it has no crosslinking site. In order to show solvent resistance, an acid generator and a crosslinking agent must be added. From these results, it can be seen that the organic film formed using the polymer of the present invention synthesized by the production method of the present invention shows sufficient solvent resistance compared to the polymer (R1) in which the number of carbon atoms at the top position of the fluorene skeleton in the repeating unit is 2. Furthermore, since the comparative UDL-3 used in Comparative Example 1-3 contains the compound (R2) having a triple bond at the terminal, it is considered that cross-linking occurs by heat treatment and sufficient solvent resistance is exhibited.

[0394] Example 2 Etching Test Using CF4 / CHF3 Gas (Examples 2-1 to 2-20, Comparative Example 2-1)

[0395] The above organic film forming compositions (UDL-1 to 20, comparative UDL-3) were coated on silicon wafer substrates and calcined at 350°C for 60 seconds in the atmosphere. An organic film of 115 nm was formed, and an etching test using CF4 / CHF3 gas was performed under the following conditions. In addition, a Telius etching device manufactured by Tokyo Electron was used to determine the difference in film thickness of the organic film before and after etching. The results are shown in Table 4.

[0396] The etching conditions are as follows.

[0397] Chamber pressure 40.0Pa

[0398] RF power 1,000W

[0399] CF4 gas flow rate 100sccm

[0400] CHF3 gas flow rate 10sccm

[0401] He gas flow rate 200 sccm

[0402] Time 20 seconds

[0403] Table 4 shows the film reduction of each of the Examples and Comparative Examples as a ratio, with the film thickness reduction of Comparative Example 2-1 by etching using CF4 / CHF3-based gas being 100. The smaller the ratio, the better the etching resistance.

[0404] Example 3 Etching Test Using O2 Gas (Examples 3-1 to 3-20, Comparative Example 3-1)

[0405] Similar to the etching test using CF4 / CHF3 gas, the organic film forming composition (UDL-1 to 20, comparative UDL-3) was applied on a silicon substrate and calcined in the atmosphere at 350°C for 60 seconds. An organic film of 115 nm was formed, and an etching test using O2 gas was performed under the following conditions. In this case, the difference in film thickness of the organic film before and after etching was obtained using an etching device Telius manufactured by Tokyo Electron. The results are shown in Table 4.

[0406] The etching conditions are as follows.

[0407] Chamber pressure 40.0Pa

[0408] RF power 100W

[0409] O2 gas flow rate 30sccm

[0410] N2 gas flow rate 70sccm

[0411] Time 20 seconds

[0412] Likewise, Table 4 shows the film reduction of each of the Examples and Comparative Examples as a ratio, with the film thickness reduction of Comparative Example 3-1 by etching using an O2-based gas being 100. The smaller the ratio, the better the etching resistance.

[0413] [Table 4]

[0414]

[0415] As shown in Table 4, in the results of Examples 3-1 to 20 using UDL-1 to 20 using the organic film forming composition of the present invention, in any etching test using CF4 / CHF3 gas and O2 gas, the amount of film reduction after etching is smaller than that of Comparative Example 3-1 using a compound without direct bonding of fluorene skeletons, and a film with excellent etching resistance can be formed.

[0416] Example 4 Pattern Formation Test 1 (Examples 4-1 to 4-20, Comparative Examples 4-1 to 4-3)

[0417] The above-mentioned organic film forming compositions (UDL-1 to 20, comparative UDL-1 to 3) were coated on silicon wafer substrates, and calcined at 350°C for 60 seconds in the atmosphere to form organic films. SOG-1 was coated thereon and baked at 220°C for 60 seconds to form a resist lower layer film with a film thickness of 35 nm. ArF single-layer resist, which was a resist upper layer film material, was coated thereon and baked at 105°C for 60 seconds to form a photoresist film with a film thickness of 100 nm. A wet protection film material (TC-1) was coated on the photoresist film and baked at 90°C for 60 seconds to form a protection film with a film thickness of 50 nm.

[0418] As for the resist upper film material (single-layer resist for ArF), it can be prepared by dissolving a polymer (RP1), an acid generator (PAG1), and a basic compound (Amine1) in a solvent containing 0.1 mass % of a surfactant FC-4430 (manufactured by Sumitomo 3M Co., Ltd.) in the proportions shown in Table 5, and filtering using a 0.1 μm fluororesin filter.

[0419] [Table 5]

[0420]

[0421] The polymer (RP1), acid generator (PAG1), and basic compound (Amine1) used are shown below.

[0422] [Chemistry 48]

[0423]

[0424] As a resist underlayer film material (SOG-1), a 2% solution of the following polymer in propylene glycol ethyl ether was prepared.

[0425] [Chemistry 49]

[0426]

[0427] The wet protective film material (TC-1) was prepared by dissolving the protective film polymer (PP1) in an organic solvent at the ratio shown in Table 6, and filtering the solution through a 0.1 μm fluororesin filter.

[0428] [Table 6]

[0429]

[0430] The polymer (PP1) used is shown below.

[0431] [Chemistry 50]

[0432]

[0433] Then, exposure was performed using an ArF immersion exposure device (manufactured by Nikon Co., Ltd.; NSR-S610C, NA1.30, σ0.98 / 0.65, 35-degree dipole s-polarized illumination, 6% half-step phase shift mask), baked (PEB) at 100°C for 60 seconds, and developed with a 2.38% by mass tetramethylammonium hydroxide (TMAH) aqueous solution for 30 seconds to obtain a positive line and space pattern of 45nm to 25nm.

[0434] Then, using a Tokyo Electron etching apparatus Telius, SOG-1 was etched by dry etching using the resist pattern as a mask to form a hard mask pattern, the organic film was etched using the obtained hard mask pattern as a mask to form an organic film pattern, and the silicon wafer was etched using the obtained organic film pattern as a mask. The etching conditions are as follows.

[0435] Transfer conditions of resist pattern to SOG-1.

[0436] Chamber pressure 10.0Pa

[0437] RF power 500W

[0438] CF4 gas flow rate 150sccm

[0439] CHF3 gas flow rate 50sccm

[0440] Time 15 sec

[0441] Transfer conditions of SOG-1 pattern onto organic film.

[0442] Chamber pressure 2.0Pa

[0443] RF power 1000W

[0444] N2 gas flow rate 80sccm

[0445] CO2 gas flow rate 200sccm

[0446] CO gas flow rate 100 sccm

[0447] Time: 60 seconds

[0448] Transfer conditions for transferring organic film patterns to silicon wafers.

[0449] Chamber pressure 15.0Pa

[0450] RF power 500W

[0451] CF4 gas flow rate 150sccm

[0452] CHF3 gas flow rate 30sccm

[0453] Time: 120 seconds

[0454] Table 7 shows the results of observing the pattern cross section using an electron microscope (S-4700) manufactured by Hitachi, Ltd.

[0455] [Table 7]

[0456]

[0457] As shown in Table 7, from the results of Examples 4-1 to 4-20 using the organic film-forming composition (UDL1 to 20) of the present invention, it was confirmed that the resist upper film pattern was finally well transferred to the substrate, and the organic film-forming composition of the present invention is suitable for use in micro-processing using a multilayer resist method. On the other hand, in Comparative Example 4-1, as shown in the solvent resistance test, it was not sufficiently hardened, so the pattern collapsed during pattern processing and a good pattern could not be obtained. In Comparative Examples 4-2 to 3, a pattern was formed. However, in Comparative Example 4-3 using a compound without direct bonding between fluorene skeletons, the minimum size without pattern distortion after substrate transfer etching was larger than that of Examples 4-1 to 4-20.

[0458] Example 5 Pattern Formation Test 2 (Examples 5-1 to 5-20, Comparative Examples 5-1 to 5-3)

[0459] On a SiO2 wafer substrate having a trench pattern (trench width 10 μm, trench depth 0.10 μm), the above-mentioned organic film forming compositions (UDL-1 to 20, comparative UDL-1 to 3) were coated respectively and calcined at 350°C for 60 seconds in the atmosphere. In addition, a laminated film was formed by the same method as in the pattern forming test 1, and patterning and dry etching were performed, and the final pattern shape was observed. The results are shown in the following Table 8.

[0460] [Table 8]

[0461]

[0462] As shown in Table 8, the results of the organic film-forming composition of the present invention (Examples 5-1 to 5-20) confirmed that the resist upper film pattern was finally well transferred to the substrate, and the organic film-forming composition of the present invention is suitable for use in micro-processing using a multilayer resist method. On the other hand, in Comparative Example 5-2, although solvent resistance was obtained to form a cured film, due to poor pattern filling, pattern collapse occurred during pattern processing, and ultimately a good pattern could not be obtained. In Comparative Example 5-1, as in Comparative Example 4-1 of Pattern Formation Test 1, it was not sufficiently cured as shown in the solvent resistance test, so pattern collapse occurred during pattern processing, and a good pattern could not be obtained. In Comparative Example 5-3, although a pattern could be formed, the minimum size without pattern distortion after substrate transfer etching was larger than that of Examples 5-1 to 5-20.

[0463] Example 6 Defect Inspection (Examples 6-1 to 6-20, Comparative Example 6-1)

[0464] The above-mentioned organic film forming compositions (UDL1 to 20, comparison UDL2) were respectively coated on a silicon wafer substrate and calcined at 350°C in the atmosphere for 60 seconds. Then, coating defects larger than 60 nm were measured on the surface of the formed organic film using a dark field defect inspection device SP2 manufactured by KLA-Tencor.

[0465] [Table 9]

[0466] Organic film forming composition Coating defects Example 6-1 UDL-1 8 Example 6-2 UDL-2 12 Embodiment 63 UDL-3 10 Example 6-4 UDL-4 9 Example 6-5 UDL-5 14 Example 6-6 UDL-6 13 Embodiment 6-7 UDL-7 20 Embodiment 6-8 UDL-8 25 Embodiment 6-9 UDL-9 21 Embodiment 6-10 UDL-10 9 Embodiment 6-11 UDL-11 11 Examples 6-12 UDL-12 13 Embodiment 6-13 UDL-13 9 Embodiment 6-14 UDL-14 8 Embodiment 6-15 UDL-15 10 Embodiment 6-16 UDL-16 13 Embodiment 6-17 UDL-17 12 Embodiment 6-18 UDL-18 11 Example 6-19 UDL-19 14 Embodiment 6-20 UDL-20 10 Comparative Example 6-1 Compare UDL-2 78

[0467] As shown in Table 9, in Examples 6-1 to 6-20 using UDL-1 to UDL-20 of the present invention, the number of coating defects after forming an organic film is less than that of Comparative Example 6-1, and the number of defects is suppressed. It is believed that the solvent solubility of the compounds (polymers) used in Examples 6-1 to 6-20 is high, so the generation of insoluble components is small, and the occurrence of coating defects is suppressed. On the other hand, it is believed that the polymerization number of carbon atoms at the top of the fluorene skeleton of the polymer R1 used in Comparative Example 6-1 is 2, the solvent solubility is low, and the generation of insoluble components is large, so many coating defects occur.

[0468] In addition, the solvent solubility tested in the defect inspection is a test of the solubility of the polymer in the composition in the organic solvent. On the other hand, the solvent resistance shown in Table 3 is the solvent resistance of the organic film obtained by calcining the coating film formed by coating each composition on the substrate. Please note that it is different from the solubility of the polymer in the defect inspection in the organic solvent.

[0469] As described above, the coating type organic film-forming composition of the present invention containing the organic film-forming polymer of the present invention has good dry etching resistance and high filling / planarization characteristics, and is therefore extremely useful as an organic film material used in a multilayer resist method. Furthermore, the pattern forming method of the present invention using the composition can form a fine pattern with high precision even if the workpiece is a substrate having a height difference. Furthermore, it is known that the occurrence of defects is suppressed due to the high solvent solubility.

[0470] The present invention is not limited to the above-described embodiments. The above-described embodiments are illustrative, and those having substantially the same configuration as the technical concept described in the claims of the present invention and having the same functions and effects are all within the technical scope of the present invention.

[0471] Description of Reference Numerals

[0472] 1:Substrate

[0473] 2: Processing layer

[0474] 2a: Pattern formed on the processed layer

[0475] 3: Organic film

[0476] 3a: Organic film pattern

[0477] 4: Silicon-containing resist lower layer film

[0478] 4a: Silicon-containing resist lower film pattern

[0479] 5: Resist upper film

[0480] 5a: Resist pattern

[0481] 6: Exposure part

Claims

1. A coating type organic film forming composition, characterized in that it contains: A polymer having a partial structure represented by the following general formula (2); and Organic solvents; In formula (2), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may have a substituent, W1 is an aryl group having 6 to 30 carbon atoms which may have a substituent, and W2 is an organic group having any one of the following structures:

2. The coating-type organic film-forming composition according to claim 1, wherein The polymer further has a partial structure represented by the following general formula (3): In formula (3), the ring structures Ar1 and Ar2 are the ring structures Ar1 and Ar2 in formula (2), and W3 is a hydrogen atom.

3. The coating-type organic film-forming composition according to claim 1, wherein The weight average molecular weight of the polymer is 500 to 5,000.

4. The coating-type organic film-forming composition according to claim 1, wherein The organic solvent is a mixture of one or more organic solvents having a boiling point of less than 160° C. and one or more organic solvents having a boiling point of 160° C. or higher.

5. The coatable organic film-forming composition according to claim 1, further comprising one or more of an acid generator, a crosslinking agent, a surfactant and a plasticizer.

6. A pattern forming method, characterized in that: An organic film is formed on a workpiece using the coating type organic film-forming composition according to any one of claims 1 to 5, forming a silicon-containing resist underlayer film on the organic film using a silicon-containing resist underlayer film material, forming a resist upper film on the silicon-containing resist lower film using a photoresist composition, forming a circuit pattern on the upper layer of the resist, The patterned resist upper film is used as a mask to etch the silicon-containing resist lower film, thereby transferring the pattern to the silicon-containing resist lower film. The organic film is etched using the silicon-containing resist lower layer film having the transferred pattern as a mask to transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby forming a pattern on the object to be processed.

7. A pattern forming method, characterized in that: An organic film is formed on a workpiece using the coating type organic film-forming composition according to any one of claims 1 to 5, forming a silicon-containing resist underlayer film on the organic film using a silicon-containing resist underlayer film material, forming an organic anti-reflective film on the silicon-containing resist underlayer film, A photoresist composition is used to form a resist upper film on the organic anti-reflection film to form a 4-layer film structure. forming a circuit pattern on the upper layer of the resist, The organic anti-reflection film and the silicon-containing resist lower film are etched using the patterned resist upper film as a mask to transfer the pattern to the organic anti-reflection film and the silicon-containing resist lower film. The organic film is etched using the silicon-containing resist lower layer film having the transferred pattern as a mask to transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby forming a pattern on the object to be processed.

8. A pattern forming method, characterized in that: An organic film is formed on a workpiece using the coating type organic film-forming composition according to any one of claims 1 to 5, forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film on the organic film, forming a resist upper layer film on the inorganic hard mask using a photoresist composition, forming a circuit pattern on the upper layer of the resist, The inorganic hard mask is etched using the patterned resist upper layer film as a mask to transfer the pattern to the inorganic hard mask. The inorganic hard mask having the transferred pattern is used as a mask to etch the organic film to transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the organic film to which the pattern is transferred as a mask, thereby forming a pattern on the object to be processed.

9. A pattern forming method, characterized in that: An organic film is formed on a workpiece using the coating type organic film-forming composition according to any one of claims 1 to 5, forming an inorganic hard mask film selected from a silicon oxide film, a silicon nitride film and a silicon oxide nitride film on the organic film, forming an organic anti-reflection film on the inorganic hard mask, A photoresist composition is used to form a resist upper film on the organic anti-reflection film to form a 4-layer film structure. forming a circuit pattern on the upper layer of the resist, The organic anti-reflection film and the inorganic hard mask are etched using the patterned resist upper film as a mask to transfer the pattern to the organic anti-reflection film and the inorganic hard mask. The inorganic hard mask film having the pattern formed thereon is used as a mask to etch the organic film and transfer the pattern to the organic film. Furthermore, the object to be processed is etched using the patterned organic film as a mask to form a pattern on the object to be processed.

10. The pattern forming method according to claim 8 or 9, wherein: The inorganic hard mask is formed by a CVD method or an ALD method.

11. The pattern forming method according to any one of claims 6 to 9, wherein: The resist upper layer film pattern forming method forms a pattern by optical lithography using light with a wavelength of 10 nm to 300 nm, direct writing using an electron beam, nanoimprinting, or a combination thereof.

12. The pattern forming method according to any one of claims 6 to 9, wherein: The method for forming a pattern of the resist upper layer film includes alkali development or development using an organic solvent.

13. The pattern forming method according to any one of claims 6 to 9, wherein: The object to be processed is a semiconductor device substrate, a metal film, a metal carbide film, a metal oxide film, a metal nitride film, a metal oxide carbide film or a metal oxide nitride film.

14. The pattern forming method according to any one of claims 6 to 9, wherein: The workpiece includes silicon, titanium, tungsten, hafnium, zirconium, chromium, germanium, copper, silver, gold, aluminum, indium, gallium, arsenic, palladium, iron, tantalum, iridium, molybdenum or an alloy thereof.

15. A polymer having a partial structure represented by the following general formula (2); In formula (2), the ring structures Ar1 and Ar2 represent a benzene ring or a naphthalene ring which may have a substituent, W1 is an aryl group having 6 to 30 carbon atoms which may have a substituent, and W2 is an organic group having any one of the following structures:

16. The polymer according to claim 15, further comprising a partial structure represented by the following general formula (3); In formula (3), the ring structures Ar1 and Ar2 are the ring structures Ar1 and Ar2 in formula (2), and W3 is a hydrogen atom.

17. The polymer according to claim 15, which has a weight average molecular weight of 500 to 5000.

18. A method for producing a polymer, which is a method for producing the polymer according to claim 15, characterized in that: The polymer is synthesized by copolymerizing a fluorenol having the aromatic group W1 and a tertiary alcohol group with a compound having the organic group W2 as a partial structure.

19. A method for producing a polymer, which is a method for producing the polymer according to claim 15, characterized in that: The polymer is synthesized by using a fluorenol having the aromatic group W1 and a tertiary alcohol group as a monomer and utilizing an electrophilic substitution reaction on the fluorene ring accompanied by dehydration. In the synthesis of the polymer, a compound having the organic group W2 as a partial structure is added.

20. A method for producing a polymer, which is a method for producing the polymer according to claim 16, characterized in that: The fluorenols having the aromatic group W1 and a tertiary alcohol group are copolymerized with the fluorenols having a secondary alcohol group.

21. A method for producing a polymer, which is a method for producing the polymer according to claim 16, characterized in that: Using one of the first fluorenols having the aromatic group W1 and a tertiary alcohol group or the second fluorenols having a secondary alcohol group as a monomer, the polymer is synthesized by an electrophilic substitution reaction on the fluorene ring accompanied by dehydration to obtain a first polymer; The other of the first fluorenol and the second fluorenol is added to the first polymer and further polymerized to obtain the polymer according to claim 16 as the second polymer.

Citation Information

Patent Citations

  • Reducing alkylation of aromatic nitro compound and ketone or aldehyde

    JP1985094947A

  • Method and device for forming silicon nitride film, and method for preprocessing of cleaning thereof

    JP2002334869A

  • Pattern forming method, and material for forming underlayer film

    JP2004205685A

  • Material for forming photoresist lower layer film and method for forming pattern

    JP2005128509A

  • Resist underlayer film material and pattern forming method

    JP2005250434A